Polycarbonate resin composition and molded article

By introducing a combination of specific polydimethylsiloxane copolymer and methyl ethyl ester modified polyorganosiloxane into the polycarbonate resin, the problems of insufficient low-temperature impact resistance and black products are solved, and efficient impact resistance and excellent appearance performance are achieved.

JP7670531B2Active Publication Date: 2025-04-30TEIJIN LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021064626
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-06
Publication Date
2025-04-30
Estimated Expiration
2041-04-06

AI Technical Summary

Technical Problem

The prior art is difficult to achieve efficient impact resistance and prevent problems caused by black products under low temperature conditions, which affects the appearance and performance of the material.

Method used

Using a combination of polycarbonate resins containing specific polycarbonate and polydimethylsiloxane copolymers and methyl ethyl methylate modified polyorganosiloxanes, the structure and composition of the resin are optimized to improve low temperature impact resistance and prevent the production of black products.

Benefits of technology

It significantly improves the low-temperature impact resistance of the resin, avoids the generation of black products, improves the appearance and performance of the material, making it suitable for outdoor structural members and automotive-related components, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007670531000001
    Figure 0007670531000001
  • Figure 0007670531000002
    Figure 0007670531000002
  • Figure 0007670531000003
    Figure 0007670531000003
Patent Text Reader

Abstract

To provide a polycarbonate resin composition that has a good molding appearance with reduced black bumps and dramatically improved low-temperature impact resistance.SOLUTION: The present invention discloses a polycarbonate resin composition. Relative to 100 pts.wt. of (A) a resin component (A component) comprising (A-1) a polycarbonate-polydiorganosiloxane copolymer 1-100 pts.wt., which comprises an aromatic polycarbonate block and a polydiorganosiloxane block represented by the general formula [3], and (A-2) an aromatic polycarbonate resin 0-99 pts.wt., the polycarbonate resin composition comprises (B) a methacryl-modified polyorganosiloxane (B component) 0.3-2.5 pts.wt.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polycarbonate resin composition and a molded article. More specifically, the present invention relates to a polycarbonate resin composition that uses a specific polycarbonate-polydiorganosiloxane copolymer and a (meth)acrylic-modified polyorganosiloxane to provide a good molded appearance with reduced black spots and significantly improved low-temperature impact resistance. [Background technology]

[0002] Polycarbonate resins are used in many applications, such as machine parts, automobile parts, electrical and electronic parts, and office equipment parts, due to their excellent properties, such as mechanical strength, dimensional stability, and flame retardancy. With their strength in impact resistance, they are sometimes used as housings and exterior parts for various devices, but as their applications expand, the environments in which they are used are also diversifying, and sufficient performance is required even outdoors, at low temperatures such as -30°C, and when exposed to paint or chemicals. For example, sufficient performance has not been obtained as a material for outdoor electrical and electronic storage boxes such as information and communication boxes, junction boxes for solar power generation, and the like, which require very high impact properties. A polycarbonate-based material, polycarbonate-polydiorganosiloxane copolymer (hereinafter sometimes abbreviated as "PC-POS copolymer"), is known as a resin material with high low-temperature impact resistance (Patent Document 1). Polycarbonate-polydiorganosiloxane copolymers have superior low-temperature impact resistance and flame retardancy compared to conventional polycarbonate resins, and attempts have been made to improve low-temperature impact resistance by appropriately selecting the polydiorganosiloxane (hereinafter sometimes abbreviated as "POS") skeleton and manufacturing method to be applied and controlling the domain state of POS aggregation (Patent Documents 2 and 3). In addition, a method of improving low-temperature impact resistance by blending a rubber-like elastomer or polyolefin with a PC-POS copolymer has also been disclosed (Patent Documents 4 and 5), but the low-temperature impact resistance is still insufficient. On the other hand, as a method of improving low-temperature impact resistance, a polycarbonate-polydiorganosiloxane copolymer using a long-chain POS with a large POS repeat number has been disclosed (Patent Document 2), but this often causes molded appearance defects such as black spots and the associated blackening, leading to a decrease in aesthetics and uneven coloring in design, making it difficult to use as an exterior material. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 5-247195 [Patent Document 2] Special Publication No. 2006-523243 [Patent Document 3] WO91 / 00885 [Patent Document 4] Japanese Patent Application Publication No. 4-225060 [Patent Document 5] WO2016 / 088861 issue Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide a polycarbonate resin composition and a molded article which have a good molded appearance with reduced foreign matter and which have significantly improved low-temperature impact resistance. [Means for solving the problem]

[0005] As a result of intensive research to solve the above problems, the present inventors discovered that the above problems can be solved by the following configuration, and arrived at the present invention.

[0006] (Configuration 1) (A) (A-1) a polycarbonate block represented by the following general formula [1] and a polycarbonate block represented by the following general formula A polycarbonate resin composition comprising 100 parts by weight of a resin component (A) consisting of 1 to 100 parts by weight of a polycarbonate-polydiorganosiloxane copolymer consisting of a polydiorganosiloxane block represented by [3] and 0 to 99 parts by weight of (A-2) an aromatic polycarbonate resin consisting of a polycarbonate block represented by the following general formula [1], and 0.3 to 2.5 parts by weight of (B) a (meth)acrylic-modified polyorganosiloxane (B component).

[0007] [ka]

[0008] [(In the above general formula [1], R 1 and R 2each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of each of these groups, they may be the same or different, e and f each represent an integer of 1 to 4, and W represents a single bond or at least one group selected from the group consisting of groups represented by the following general formula [2]:

[0009] [ka]

[0010] (In the above general formula [2], R 11 ,R 12 ,R 13 ,R 14 ,R 15 ,R 16 ,R 17 and R 18 each independently represents a group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms; R 19 and R 20 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of groups, they may be the same or different, g is an integer from 1 to 10, and h is an integer from 4 to 7.)

[0011] [ka]

[0012] (In the above general formula [3], R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; R 9 and R 10 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and the average chain length p+q is a natural number of 50 to 120. X is a divalent aliphatic group having 2 to 8 carbon atoms.

[0013] (Configuration 2) The polycarbonate resin composition according to the above-mentioned configuration 1, characterized in that p+q in the above-mentioned formula [3] is 50 to 70. (Configuration 3) 3. The polycarbonate resin composition according to configuration 1 or 2, wherein the content of the polydiorganosiloxane block represented by the above formula [3] in component A-1 is 4 to 20% by weight. (Configuration 4) 4. The polycarbonate resin composition according to any one of the above configurations 1 to 3, wherein the content of the polydiorganosiloxane block represented by the above formula [3] in component A is 2.5 to 6.5% by weight. (Configuration 5) 5. The polycarbonate resin composition according to any one of the above configurations 1 to 4, wherein the viscosity average molecular weight of component A-1 is 11,000 to 30,000.

[0014] (Configuration 6) 5. The polycarbonate resin composition according to claim 4, which satisfies (i) to (iii). (i) In the cross-sectional image of component A observed using an electron microscope,2 ) there are 1 to 20 domains with a maximum diameter of 80 nm or more. (ii) The average domain size is 30 to 100 nm. (iii) In the cross-sectional observation images of component A using an electron beam microscope, all five sample slices had a size of 850 nm square (722,500 nm 2 ) there are no domains with a maximum diameter of 400 nm or more. (Configuration 7) The polycarbonate resin composition according to any one of the above structures 1 to 6, characterized in that the polydiorganosiloxane block represented by the above formula [3] is a polydiorganosiloxane block derived from a (2-allylphenol)-terminated polydiorganosiloxane or a (2-methoxy-4-allylphenol)-terminated polydiorganosiloxane. (Configuration 8) R in the above formula [3] 3 , R 4 , R 5 , R 6 , R 7 and R 8 The polycarbonate resin composition according to any one of the above configurations 1 to 7, wherein is a methyl group. (Configuration 9) The polycarbonate block represented by the formula [1] is a polycarbonate block derived from 2,2-bis(4-hydroxyphenyl)propane. The polycarbonate resin composition according to any one of configurations 1 to 8. (Configuration 10) The polycarbonate resin composition according to any one of the above structures 1 to 9, characterized in that component B is an acrylic-modified polyorganosiloxane obtained by graft copolymerizing a (meth)acrylic acid ester (component B2) with a polyorganosiloxane (component B1) represented by the following general formula [4]:

[0015] [ka]

[0016] [In the above general formula [4], R 1 , R 2 and R 3 each independently represents a hydrocarbon group having 1 to 20 carbon atoms or a halogenated hydrocarbon group having 1 to 20 carbon atoms, and Y represents an organic group having at least one group selected from the group consisting of a radical reactive group selected from the group consisting of a vinyl group, an allyl group, and a γ-(meth)acryloxypropyl group, and an SH group. 1 and X 2 each independently represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or SiR 4 R 5 R 6 (R 4 , R 5 each independently represents a hydrocarbon group having 1 to 20 carbon atoms or a halogenated hydrocarbon group having 1 to 20 carbon atoms; R 6 represents a hydrocarbon group having 1 to 20 carbon atoms, a halogenated hydrocarbon group having 1 to 20 carbon atoms, or an organic group having at least one group selected from the group consisting of a radical reactive group selected from the group consisting of a vinyl group, an allyl group, and a γ-(meth)acryloxypropyl group, and an SH group), m is an integer of 1 to 10,000, n is an integer of 1 or more, and the siloxane chain may be branched.]

[0017] (Configuration 11) In the above formula [4], R 1 ,R 2 ,R 3 11. The polycarbonate resin composition according to claim 10, wherein is a methyl group. (Configuration 12) 12. The polycarbonate resin composition according to claim 10 or 11, wherein component B2 is methyl methacrylate and / or 2-hydroxyethyl methacrylate. (Configuration 13) The L measured according to JIS Z 8781-4 for the molded product obtained by continuous molding for 25 shots at a molding temperature of 280°C. * Maximum color difference ΔL of the value * 13. The polycarbonate resin composition according to any one of the above configurations 1 to 12, wherein the value is 3 or less. (Configuration 14) The polycarbonate resin composition according to any one of the above configurations 1 to 13, characterized in that it contains 0.001 to 20 parts by weight of a flame retardant (C) (component C) per 100 parts by weight of component A. (Configuration 15) 15. The polycarbonate resin composition according to any one of the above configurations 1 to 14, comprising 0.01 to 5 parts by weight of a fluorinated anti-dripping agent (D) (Component D) per 100 parts by weight of Component A. (Configuration 16) 16. A molded article formed from the polycarbonate resin composition according to any one of the above items 1 to 15. Effect of the Invention

[0018] The polycarbonate resin composition of the present invention has good low-temperature impact resistance and is free from blackening due to black spots. Since it has a molded appearance without defects, it is suitable for use as a material for outdoor structural members for cold regions, various housing members, and automobile-related parts. It is also useful for various electronic and electrical device parts, camera parts, office automation device parts, precision machinery parts, machinery parts, vehicle parts, and other agricultural materials, transport containers, play equipment, and miscellaneous goods, and its industrial effects are exceptional. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] (Component A: resin component) The resin component of the present invention comprises 1 to 100 parts by weight of a polycarbonate-polydiorganosiloxane copolymer (A-1) and 0 to 99 parts by weight of an aromatic polycarbonate resin (A-2).

[0020] (A-1 component: polycarbonate-polydiorganosiloxane copolymer) In the present invention, the polycarbonate-polydiorganosiloxane copolymer (hereinafter sometimes abbreviated as PC-POS copolymer) is a polycarbonate-polydiorganosiloxane copolymer consisting of a polycarbonate block represented by formula [1] and a polydiorganosiloxane block represented by formula [3].

[0021] <Polycarbonate block represented by formula [1]> In the present invention, the polycarbonate block is represented by the following formula [1].

[0022] [ka]

[0023] In the above formula [1], R 1 and R 2 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of each, they may be the same or different.

[0024] Examples of halogen atoms include fluorine, chlorine, and bromine atoms. Examples of alkyl groups having 1 to 18 carbon atoms include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, dodecyl, and tetradecyl groups. Preferred are alkyl groups having 1 to 6 carbon atoms. Examples of alkoxy groups having 1 to 18 carbon atoms include methoxy, ethoxy, propoxy, butoxy, pentoxy, hexoxy, and octoxy groups. Preferred are alkoxy groups having 1 to 6 carbon atoms. Examples of cycloalkyl groups having 6 to 20 carbon atoms include cyclohexyl and cyclooctyl groups. Preferred are cycloalkyl groups having 6 to 12 carbon atoms. Examples of cycloalkoxy groups having 6 to 20 carbon atoms include cyclohexyloxy and cyclooctyloxy groups. Preferred are cycloalkyl groups having 6 to 12 carbon atoms. Examples of the alkenyl group having 2 to 10 carbon atoms include a methenyl group, an ethenyl group, a propenyl group, a butenyl group, and a pentenyl group. An alkenyl group having 2 to 6 carbon atoms is preferable. Examples of the aryl group having 6 to 14 carbon atoms include a phenyl group and a naphthyl group. Examples of the aryloxy group having 6 to 14 carbon atoms include a phenyloxy group and a naphthyloxy group. Examples of the aralkyl group having 7 to 20 carbon atoms include a benzyl group and a phenylethyl group. Examples of the aralkyloxy group having 7 to 20 carbon atoms include a benzyloxy group and a phenylethyloxy group.

[0025] e and f each independently represents an integer of 1 to 4.

[0026] W is a single bond or at least one group selected from the group consisting of groups represented by the following formula [2]:

[0027] [ka]

[0028] In the above formula [2], R 11 , R 12 , R 13 , R14 , R 15 , R 16 , R 17 and R 18 each independently represents a group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms.

[0029] Examples of the alkyl group having 1 to 18 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, and a dodecyl group. An alkyl group having 1 to 6 carbon atoms is preferable. Examples of the aryl group having 6 to 14 carbon atoms include a phenyl group, a naphthyl group, and the like. These may be substituted. Examples of the substituent include an alkyl group having 1 to 6 carbon atoms, such as a methyl group, an ethyl group, a propyl group, and a butyl group. Examples of the aralkyl group having 7 to 20 carbon atoms include a benzyl group, a phenylethyl group, and the like.

[0030] R 19 and R 20 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of such groups, they may be the same or different.

[0031] Examples of halogen atoms include fluorine, chlorine, and bromine atoms. Examples of alkyl groups having 1 to 18 carbon atoms include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, dodecyl, and tetradecyl groups. Preferred are alkyl groups having 1 to 6 carbon atoms. Examples of alkoxy groups having 1 to 10 carbon atoms include methoxy, ethoxy, propoxy, butoxy, and pentoxy groups. Preferred are alkoxy groups having 1 to 6 carbon atoms. Examples of cycloalkyl groups having 6 to 20 carbon atoms include cyclohexyl and cyclooctyl groups. Preferred are cycloalkyl groups having 6 to 12 carbon atoms. Examples of cycloalkoxy groups having 6 to 20 carbon atoms include cyclohexyloxy and cyclooctyl groups. Preferred are cycloalkyl groups having 6 to 12 carbon atoms. Examples of the alkenyl group having 2 to 10 carbon atoms include a methenyl group, an ethenyl group, a propenyl group, a butenyl group, and a pentenyl group. An alkenyl group having 2 to 6 carbon atoms is preferable. Examples of the aryl group having 6 to 14 carbon atoms include a phenyl group and a naphthyl group. Examples of the aryloxy group having 6 to 14 carbon atoms include a phenyloxy group and a naphthyloxy group. Examples of the aralkyl group having 7 to 20 carbon atoms include a benzyl group and a phenylethyl group. Examples of the aralkyloxy group having 7 to 20 carbon atoms include a benzyloxy group and a phenylethyloxy group.

[0032] g is an integer of 1 to 10, preferably an integer of 1 to 6. h is an integer of 4 to 7, preferably an integer of 4 to 5.

[0033] The polycarbonate block represented by the formula [1] is preferably a polycarbonate block derived from 2,2-bis(4-hydroxyphenyl)propane.

[0034] The length of the polycarbonate block is preferably 10 to 100, more preferably 30 to 100, and even more preferably 50 to 70, in terms of the average number of repeating units of the formula [1].

[0035] The content of the polycarbonate block represented by the formula [1] is preferably 50 to 99.9% by weight, more preferably 70 to 99.5% by weight, and even more preferably 80 to 99.0% by weight, based on the total weight of the copolymer.

[0036] <Polydiorganosiloxane block represented by formula [3]> In the present invention, the polydiorganosiloxane block is represented by the following formula [3].

[0037] [ka]

[0038] In the above formula [3], R 3 , R 4 , R 5 , R 6 , R 7 and R 8 each independently represents a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms.

[0039] Examples of the alkyl group having 1 to 12 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, and a dodecyl group. An alkyl group having 1 to 6 carbon atoms is preferable. Examples of the substituted or unsubstituted aryl group having 6 to 12 carbon atoms include a phenyl group and a naphthyl group. Examples of the substituent include an alkyl group having 1 to 12 carbon atoms such as a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, and a hexyl group. R 3 , R 4 , R 5 , R 6 , R 7 and R 8 is preferably a methyl group.

[0040] R 9 and R 10are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms.

[0041] Examples of the halogen atom include a fluorine atom, a chlorine atom, and a bromine atom. Examples of the alkyl group having 1 to 10 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, Examples of the alkoxy group having 1 to 10 carbon atoms include a methoxy group, an ethoxy group, a propoxy group, a butoxy group, a pentoxy group, a hexoxy group, a heptoxy group, an octoxy group, and the like. An alkoxy group having 1 to 6 carbon atoms is preferable.

[0042] X is a divalent aliphatic group having 2 to 8 carbon atoms. Examples of the divalent aliphatic group include an alkylene group having 2 to 8 carbon atoms. Examples of the alkylene group include an ethylene group, a trimethylene group, and a tetramethylene group.

[0043] The polydiorganosiloxane block represented by the above formula [3] is preferably a polydiorganosiloxane block derived from a (2-allylphenol)-terminated polydiorganosiloxane or a (2-methoxy-4-allylphenol)-terminated polydiorganosiloxane. That is, in formula [3], X is a trimethylene group and R 9 and R 10 is a hydrogen atom, or X is a trimethylene group and R 9 and R 10 is preferably a methoxy group.

[0044] The content of the polydiorganosiloxane block represented by the above formula [3] is preferably 4 to 20% by weight, more preferably 8 to 15% by weight, and even more preferably 12 to 15% by weight, based on the total weight of the polycarbonate-polydiorganosiloxane copolymer. If the content is less than the lower limit, the formation of maximum domains may be insufficient and low-temperature impact resistance may not be exhibited, while if the content is more than the upper limit, there may be major problems in terms of production, such as poor polymerization reaction due to deterioration of the emulsion state and difficulty in granulation due to an excessively low glass transition temperature.

[0045] The viscosity average molecular weight of the A-1 component is preferably 11,000 to 30,000, more preferably 13,000 to 25,000, further preferably 15,000 to 20,000, and particularly preferably 15,000 to 18,000. If the viscosity average molecular weight of the A-1 component is less than the lower limit, it may be difficult to obtain practical mechanical strength in many fields, and the kneadability may deteriorate due to a large difference in melt viscosity with the polycarbonate resin (A-2 component) to be mixed, and if it exceeds the upper limit, the melt viscosity is high and generally a high molding processing temperature is required, which may lead to problems such as thermal deterioration of the resin and a decrease in productivity due to poor separation in the water washing step during production.

[0046] p is a natural number, q is 0 or a natural number, and the average chain length p+q is a natural number from 50 to 120. The average chain length p+q is preferably a natural number from 50 to 100, more preferably a natural number from 50 to 70, and even more preferably a natural number from 60 to 70. If the average chain length p+q is less than 50, sufficient low-temperature impact resistance is not exhibited, and if it is more than 120, poor marbled appearance and surface peeling occur.

[0047] (Aromatic polycarbonate resin (A-2)) The aromatic polycarbonate resin (A-2) in the present invention is derived from a dihydric phenol (I) represented by the general formula [5].

[0048] [ka]

[0049] (In the above general formula [5], R 1 , R 2 , e, f and W are the same as in equation [1].)

[0050] Examples of the dihydric phenol include 4,4'-dihydroxybiphenyl, bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxy-3,3'-biphenyl)propane, 2,2-bis(4-hydroxy- 3-isopropylphenyl)propane, 2,2-bis(3-t-butyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)octane, 2,2-bis(3-bromo-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 1,1-bis(3-cyclohexyl-4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl) 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)cyclopentane, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dimethyldiphenyl ether, 4,4'-sulfonyldiphenol, 4,4'-dihydroxydiphenyl sulfoxide, 4,4'-dihydroxydiphenyl sulfide, 2,2'-dimethyl -4,4'-sulfonyldiphenol, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide, 2,2'-diphenyl-4,4'-sulfonyldiphenol, 4,4'-dihydroxy-3,3'-diphenyldiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-diphenyldiphenyl sulfide, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,Examples of the cyclohexane derivatives include 4-bis(4-hydroxyphenyl)cyclohexane, 1,3-bis(4-hydroxyphenyl)cyclohexane, 4,8-bis(4-hydroxyphenyl)tricyclo[5.2.1.02,6]decane, 4,4'-(1,3-adamantanediyl)diphenol, and 1,3-bis(4-hydroxyphenyl)-5,7-dimethyladamantane.

[0051] Among these, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-sulfonyldiphenol, 2,2'-dimethyl-4,4'-sulfonyldiphenol, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, and 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene are preferred, and 2,2-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane (BPZ), 4,4'-sulfonyldiphenol, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene are particularly preferred. Among these, 2,2-bis(4-hydroxyphenyl)propane, which has excellent strength and good durability, is most suitable. These may be used alone or in combination of two or more kinds.

[0052] The component A of the present invention comprises 100 to 1 parts by weight of a polycarbonate-polydiorganosiloxane copolymer (A-1) and 0 to 99 parts by weight of an aromatic polycarbonate resin (A-2). It is preferable that the composition is composed of 90 to 10 parts by weight of the A-1 component and 10 to 90 parts by weight of the A-2 component, and more preferably 50 to 20 parts by weight of the A-1 component and 50 to 80 parts by weight of the A-2 component. If the A-1 component is less than 1 part by weight, sufficient low-temperature impact resistance is not exhibited.

[0053] The content of the polydiorganosiloxane block in the present invention is preferably 2.5 to 6.5% by weight, more preferably 3.0 to 6.0% by weight, and even more preferably 3.5 to 5.5% by weight, based on the total weight of component A. If the content is less than the lower limit, sufficient low-temperature impact resistance may not be exhibited, while if it is more than the upper limit, poor appearance due to blackening caused by black spots or marbled appearance may easily occur, and thermomechanical properties may also be reduced.

[0054] The viscosity average molecular weight of component A is preferably 11,000 to 30,000, and more preferably 12,000 to 25,000. If it is less than 11,000, sufficient low-temperature impact resistance may not be exhibited, and if it is greater than the upper limit, an increase in solution viscosity may cause a decrease in productivity or a lack of molding flowability.

[0055] (Domain size of polydiorganosiloxane) The PC-POS copolymer of the present invention has an aggregate structure in which polydiorganosiloxane domains are dispersed in a polycarbonate polymer matrix.

[0056] In the present invention, the polydiorganosiloxane domain refers to a domain mainly composed of polydiorganosiloxane dispersed in a polycarbonate matrix, and may contain other components. As described above, the polydiorganosiloxane domain is not necessarily composed of a single component because its structure is formed by phase separation from the polycarbonate matrix.

[0057] The maximum major axis, average domain size, distribution, and dispersion state of the polydiorganosiloxane domains of the component A molded product of the present invention were measured using a transmission electron microscope (hereinafter sometimes abbreviated as TEM) with a square of 850 nm (722,500 nm 2) is evaluated in a cross-sectional observation image of the resin composition. In the present invention, the terms "maximum major axis of domain" and "average domain size" refer to measurements taken by cutting a thin slice from a molded piece having a thickness of 4.0 mm formed by injection molding and observing it with a TEM. The average domain size of polydiorganosiloxane domains means the number average value of the individual domain sizes.

[0058] Specifically, a molded piece 10 mm wide, 80 mm long, and 4.0 mm thick was cut out at room temperature from a location 15 mm from the gate of the molded piece using a microtome, and observed at 20,000 times magnification with a TEM. The obtained TEM photograph was subjected to particle analysis using image analysis software WinROOF Ver.6.6 (Mitani Shoji Co., Ltd.), and the average size and particle size distribution (frequency distribution) of the polydiorganosiloxane domains in the sample thin piece were obtained. Here, the maximum major axis (the length when any two points on the outer contour of the particle are selected so that the length between them is the maximum) was used as the size of each domain. The same analysis was performed on five sample slices, and the average value was used as the value for each sample.

[0059] The average size of the polydiorganosiloxane domains in the present invention is preferably 30 to 100 nm, more preferably 40 to 80 nm, and further preferably 50 to 70 nm. If the average size is below the lower limit of this range, impact resistance may not be sufficiently exhibited, while if it exceeds the upper limit of this range, poor appearance due to black discoloration caused by black spots or poor marbled appearance may easily occur.

[0060] In the present invention, in a cross-sectional observation image of component A using a TEM, 2 ) polydiorganosiloxane with a maximum diameter of 80 nm or more Preferably, 1 to 20 domains are present, more preferably 2 to 20, even more preferably 4 to 20, and particularly preferably 5 to 20. If there is not even one polydiorganosiloxane domain with a maximum major axis of 80 nm or more, sufficient low-temperature impact resistance may not be exhibited, and if there are more than 20 domains, poor appearance due to black discoloration caused by black spots and poor appearance with a marbled appearance may easily occur. Furthermore, in the present invention, polydiorganosiloxane domains with a maximum major axis of 400 nm or more are present within an area of ​​850 nm square (722,500 nm 2 If one or more polydiorganosiloxane domains having a maximum major axis of 400 nm or more are present, the appearance may be adversely affected by significant black spots, such as black discoloration or marbled appearance.

[0061] (Polydiorganosiloxane) In the present invention, a polydiorganosiloxane having a specific average chain length and represented by the following general formula [6], hydroxyaryl-terminated polydiorganosiloxane (II), is used as a raw material.

[0062] [ka]

[0063] (In the above general formula [6], R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; R 9 and R 10 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and the average chain length p+q is a natural number of 50 to 120. X is a divalent aliphatic group having 2 to 8 carbon atoms.

[0064] The average chain length p+q is preferably a natural number of 50 to 100, more preferably a natural number of 50 to 70, and particularly preferably a natural number of 60 to 70. If the average chain length p+q is less than 50, sufficient low-temperature impact resistance is not exhibited, and if it is greater than 120, poor marbled appearance and surface peeling occur. In addition, in order to satisfy such a specific chain length range, two or more different hydroxyaryl-terminated polydiorganosiloxane (II) raw materials having average chain lengths p+q may be mixed to prepare the polydiorganosiloxane. In that case, it is preferable to use polydiorganosiloxane (E-1) having an average chain length p+q of 1 or more and less than 60, and polydiorganosiloxane (E-2) having an average chain length p+q of 60 or more and 200 or less as raw materials. The method for mixing and preparing the polydiorganosiloxane raw material may be either a method of mixing appropriate polydiorganosiloxane raw materials whose ends have been hydroxyaryl-modified together, or a method of premixing polydiorganosiloxane precursors having an appropriate average chain length before the ends are hydroxyaryl-modified together, and then modifying the ends with hydroxyaryls. The average chain length p+q is calculated by nuclear magnetic resonance (NMR) measurement.

[0065] When the polydiorganosiloxane (E-1) and the polydiorganosiloxane (E-2) are mixed, the weight ratio of (E-1):(E-2) is preferably 1:99 to 99:1, and more preferably 10:90 to 90:10.

[0066] It is more preferable to use, as the polydiorganosiloxane raw material, polydiorganosiloxane (E) obtained by previously blending the above-mentioned polydiorganosiloxanes (E-1) and (E-2). The blending ratio is preferably 1:99 to 99:1 by weight, similar to the above-mentioned (E-1):(E-2) weight ratio, and more preferably 10:90 to 90:10.

[0067] When blended in advance, the lower limit of the average chain length p+q of the polydiorganosiloxane (E-1) is preferably 1 or more, more preferably 20 or more, and even more preferably 30 or more, and the upper limit is preferably less than 60, more preferably less than 50, and even more preferably less than 45. The lower limit of the average chain length p+q of the polydiorganosiloxane (E-2) is preferably 60 or more, more preferably 70 or more, and even more preferably 90 or more, and the upper limit is preferably 200 or less, and more preferably 100 or less. As the hydroxyaryl-terminated polydiorganosiloxane (II) represented by the general formula [6], for example, the following compounds are preferably used.

[0068] [ka]

[0069] Hydroxyaryl-terminated polydiorganosiloxane (II) is a phenol having an olefinic unsaturated carbon-carbon bond, and is easily produced by subjecting vinylphenol, 2-allylphenol, isopropenylphenol, or 2-methoxy-4-allylphenol to a hydrosilylation reaction at the end of a polysiloxane chain having a predetermined degree of polymerization. Among these, (2-allylphenol)-terminated polydiorganosiloxane and (2-methoxy-4-allylphenol)-terminated polydiorganosiloxane are preferred, and (2-allylphenol)-terminated polydimethylsiloxane and (2-methoxy-4-allylphenol)-terminated polydimethylsiloxane are particularly preferred.

[0070] <Production method of polycarbonate-polydiorganosiloxane copolymer> The polycarbonate-polydiorganosiloxane copolymer of the present invention can be produced by the steps (i) and (ii).

[0071] (Step (i)) Step (i) is a step of reacting a dihydric phenol (I) represented by the following formula [5] with phosgene in a mixed solution of a water-insoluble organic solvent and an alkaline aqueous solution to prepare a solution containing a carbonate oligomer having a terminal chloroformate group.

[0072] [ka]

[0073] (In the formula, R 1 , R 2 , e, f and W are the same as above.)

[0074] As the dihydric phenol (I) represented by the formula [5], for example, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-sulfonyldiphenol, 2,2'-dimethyl-4,4'-sulfonyldiphenol, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, and 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene are preferable.

[0075] In particular, 2,2-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane (BPZ), 4,4'-sulfonyldiphenol, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene are preferred. Among them, 2,2-bis(4-hydroxyphenyl)propane, which has excellent strength and good durability, is most preferred. These may be used alone or in combination of two or more.

[0076] The PC-POS copolymer of the present invention can be produced by following the known production methods described in, for example, WO2011 / 013846 and WO2019 / 124556, but the following method is suitable when it is particularly desired to improve low-temperature impact resistance. In order to form coarse domains of 80 nm or more that improve low-temperature impact resistance, it is effective to react a polydiorganosiloxane at a high concentration with a carbonate oligomer having a terminal chloroformate group, which can produce a dispersion state that has not been seen before even in areas with a low content of siloxane blocks. Furthermore, as described above, a polydiorganosiloxane having a specific average chain length is used as a raw material, and only one type of hydroxyaryl-terminated polydiorganosiloxane (II) may be used, or two or more types may be used. Specifically, a raw material represented by the hydroxyaryl-terminated polydiorganosiloxane (II) represented by the above general formula [6] and having an average chain length p+q of 50 to 120 is used. In order to satisfy such a specific chain length range, two or more different types of hydroxyaryl-terminated polydiorganosiloxane (II) raw materials having an average chain length p+q may be mixed and used. In that case, it is preferable to use a polydiorganosiloxane (E-1) having an average chain length p+q of 1 or more and less than 60 and a polydiorganosiloxane (E-2) having an average chain length p+q of 60 or more and 200 or less as raw materials to prepare the polydiorganosiloxane, or to use a raw material obtained by premixing polydiorganosiloxane precursors having an appropriate average chain length before the terminals are modified with hydroxyaryls and then modifying the terminals with hydroxyaryls. Furthermore, the polydiorganosiloxane (E-1) and the polydiorganosiloxane (E-2) may be mixed in advance before reacting with the carbonate precursor and the dihydric phenol, or may be added to the reaction solution in parallel without being mixed in advance, or (E-1) and (E-2) may be divided and added successively to the reaction solution to react with the carbonate precursor and the dihydric phenol.More preferably, the polydiorganosiloxane (E-1) is added to the reaction solution, and then the polydiorganosiloxane (E-2) is added to the reaction solution to react with the carbonate precursor and the dihydric phenol. This is advantageous in terms of efficiency and cost effectiveness due to simplification of the manufacturing process equipment, and in the formation of domains of 80 nm or more that contribute to improved impact resistance. By adding the polydiorganosiloxane (E-2) alone last, it is thought that the local introduction of polydiorganosiloxane blocks with a large average chain length into the polymer chain is easily promoted, which is advantageous in the formation of domains of 80 nm or more. In either case, it is desirable to add the hydroxyaryl-terminated polydiorganosiloxane (II) to the reaction solution as quickly as possible, and it is preferable to add it all at once. By reacting the hydroxyaryl-terminated polydiorganosiloxane (II) at a higher concentration, it is believed that the local introduction of polydiorganosiloxane blocks having a large average chain length into the polymer chain is facilitated, which is advantageous for the formation of domains of 80 nm or more. The mass ratio of the polydiorganosiloxanes (E-1) and (E-2) used as raw materials is as described above, and the carbonate precursor and dihydric phenol will be described later.

[0077] In order to form coarse domains of 80 nm or more, in the interfacial polycondensation method for obtaining the PC-POS copolymer of the present invention, the amount of the water-insoluble organic solvent per mole of the total amount of the dihydric phenols represented by the formulas [5] and [6] is preferably 8 moles or more and less than 11 moles, more preferably 8 to 9.5 moles.

[0078] The total amount of dihydric phenols means the combined amount of bisphenol and polydiorganosiloxane monomer, which are raw materials for polycarbonate.

[0079] The amount of the insoluble organic solvent is the total amount used up to the point at which the catalyst is added and the polycondensation reaction is started, and is the total amount of the amount used during the production of the polycarbonate oligomer, the amount used to dissolve the polydiorganosiloxane monomer and the terminal terminator, and the amount added to adjust the emulsified state during the interfacial polycondensation reaction.

[0080] In the interfacial polycondensation method for obtaining the PC-POS copolymer of the present invention, if the amount of the water-insoluble organic solvent per mole of the total amount of the dihydric phenol represented by formula [5] and formula [6] is less than the lower limit, the polymer quality will decrease due to deterioration of the emulsion state during polymerization, and the productivity will also decrease due to too high solution viscosity, while if the amount exceeds the upper limit, the formation of domains of 80 nm or more will be insufficient and the cryogenic impact resistance will not be expressed. Furthermore, the water-insoluble organic solvent may be added immediately after the reaction of the carbonate precursor and the dihydric phenol with the polydiorganosiloxane proceeds. Specifically, it is desirable to add 2 moles or more of the water-insoluble organic solvent per mole of the total amount of the dihydric phenol represented by formula [5] and formula [6] when the ratio of unreacted polydiorganosiloxane in the reaction solution among the polydiorganosiloxanes used becomes 10% or less. This makes it possible to ensure sufficient reaction progress while suppressing the risk of precipitation of polymer components due to high concentration.

[0081] In addition, comonomers other than the dihydric phenol (I) and hydroxyaryl-terminated polydiorganosiloxane (II) can be used in an amount of up to 10% by weight based on the total weight of the copolymer, provided that the use does not interfere with the production process of the present invention.

[0082] In the production method of the present invention, a mixed solution containing an oligomer having a terminal chloroformate group is prepared in advance by reacting a dihydric phenol (I) with a carbonate-forming compound in a mixed solution of a water-insoluble organic solvent and an aqueous alkaline solution.

[0083] In producing an oligomer of the dihydric phenol (I), the entire amount of the dihydric phenol (I) used in the method of the present invention may be converted into an oligomer at once, or a part of the oligomer may be added as a post-added monomer as a reaction raw material to the interfacial polycondensation reaction in the latter stage. The post-added monomer is added to quickly proceed with the polycondensation reaction in the latter stage, and is added when not necessary. There is no need to add it explicitly.

[0084] The method of this oligomer formation reaction is not particularly limited, but it is usually preferable to carry out the reaction in a solvent in the presence of an acid binder.

[0085] The proportion of the carbonate ester-forming compound used may be appropriately adjusted in consideration of the stoichiometric ratio (equivalent) of the reaction. When a gaseous carbonate ester-forming compound such as phosgene is used, it is preferable to employ a method of blowing the gaseous compound into the reaction system.

[0086] As the acid binder, for example, an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide, an alkali metal carbonate such as sodium carbonate or potassium carbonate, an organic base such as pyridine, or a mixture of these may be used.

[0087] The proportion of the acid binder used may be appropriately determined in consideration of the stoichiometric ratio (equivalent) of the reaction, as described above. Specifically, it is preferable to use 2 equivalents or a slightly excess amount of the acid binder relative to the number of moles of the dihydric phenol (I) used to form the oligomer (usually 1 mole corresponds to 2 equivalents).

[0088] As the solvent, a solvent inert to various reactions, such as those used in the production of known polycarbonates, may be used alone or as a mixed solvent. Representative examples include hydrocarbon solvents such as xylene, and halogenated hydrocarbon solvents such as methylene chloride and chlorobenzene. In particular, halogenated hydrocarbon solvents such as methylene chloride are preferably used.

[0089] The reaction pressure for oligomer formation is not particularly limited, and may be normal pressure, elevated pressure, or reduced pressure, but it is usually advantageous to carry out the reaction under normal pressure. The reaction temperature is selected from the range of -20 to 50°C, and in many cases, since heat is generated during polymerization, it is desirable to cool the reaction with water or ice. The reaction time depends on other conditions and cannot be specified in general, but is usually carried out for 0.2 to 10 hours.

[0090] The pH range of the oligomer formation reaction is similar to that of known interfacial reactions, and the pH is always adjusted to 10 or higher.

[0091] In the present invention, after obtaining a mixed solution containing an oligomer of dihydric phenol (I) having terminal chloroformate groups in this manner, the hydroxyaryl-terminated polydiorganosiloxane (II) is added to the dihydric phenol (I) while stirring the mixed solution, and the hydroxyaryl-terminated polydiorganosiloxane (II) and the oligomer are subjected to interfacial polycondensation to obtain a polycarbonate-polydiorganosiloxane copolymer.

[0092] In carrying out the interfacial polycondensation reaction, an acid binder may be appropriately added in consideration of the stoichiometric ratio (equivalent) of the reaction. For example, alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, alkali metal carbonates such as sodium carbonate and potassium carbonate, organic bases such as pyridine, or mixtures thereof, are used as the acid binder. Specifically, when the hydroxyaryl-terminated polydiorganosiloxane (II) used or a part of the dihydric phenol (I) as described above is added to this reaction stage as a post-added monomer, it is preferable to use 2 equivalents or more of alkali relative to the total mole number of the post-added dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) (usually 1 mole corresponds to 2 equivalents).

[0093] The polycondensation by the interfacial polycondensation reaction between the oligomer of the dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) can be carried out by vigorously stirring the mixture. It will be held.

[0094] In such a polymerization reaction, a terminal terminator or a molecular weight regulator is usually used. Examples of the terminal terminator include compounds having a monovalent phenolic hydroxyl group, such as ordinary phenol, p-tert-butylphenol, p-cumylphenol, tribromophenol, etc., as well as long-chain alkylphenols, aliphatic carboxylic acid chlorides, aliphatic carboxylic acids, hydroxybenzoic acid alkyl esters, hydroxyphenyl alkyl acid esters, and alkyl ether phenols. The amount of the terminal terminator is in the range of 100 to 0.5 mol, preferably 50 to 2 mol, relative to 100 mol of all dihydric phenol compounds used, and it is naturally possible to use two or more compounds in combination.

[0095] To accelerate the polycondensation reaction, a catalyst such as a tertiary amine, such as triethylamine, or a quaternary ammonium salt may be added.

[0096] The reaction time of the polymerization reaction needs to be relatively long in order to reduce the amount of unreacted polydiorganosiloxane components, preferably 30 minutes or more, more preferably 50 minutes or more, while stirring the reaction solution for a long period of time can cause polymer precipitation, so the reaction time is preferably 180 minutes or less, more preferably 90 minutes or less.

[0097] If desired, a small amount of an antioxidant such as sodium sulfite or hydrosulfide may be added.

[0098] The polycarbonate resin composition of the present invention can be made into a branched polycarbonate by using a branching agent in combination with the above-mentioned dihydric phenol compound. Examples of the trifunctional or higher polyfunctional aromatic compounds used in such branched polycarbonate resins include phloroglucin, phloroglucide, 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptene-2,2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, 4-{4-[1,1-bis(4- Examples of the trisphenols include trisphenols such as 1,4-dimethylbenzylphenol, tetra(4-hydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)ketone, 1,4-bis(4,4-dihydroxytriphenylmethyl)benzene, trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid, and acid chlorides thereof. Among these, 1,1,1-tris(4-hydroxyphenyl)ethane and 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane are preferred, and 1,1,1-tris(4-hydroxyphenyl)ethane is particularly preferred.

[0099] The reaction pressure may be reduced, normal, or increased, but is usually preferably normal pressure or the reaction system's own pressure. The reaction temperature is selected from the range of -20 to 50°C, and in many cases, since heat is generated during polymerization, it is desirable to cool the reaction system with water or ice. The reaction time varies depending on other conditions such as the reaction temperature and cannot be generally specified, but is usually carried out for 0.5 to 10 hours.

[0100] In some cases, the obtained polycarbonate copolymer is subjected to a suitable physical treatment (mixing, fractionation, etc.) and / or chemical treatment (polymer reaction, crosslinking treatment, partial decomposition treatment, etc.) to obtain a desired reduced viscosity [η SP It can also be obtained as a polycarbonate copolymer of [(1,2-dichlorophenyl)-1,2-difluorophenyl] and [(1,2-dichlorophenyl)-1,2-difluorophenyl].

[0101] The reaction product (crude product) thus obtained is subjected to various post-treatments such as known separation and purification methods to obtain the desired product. It is possible to recover a polycarbonate-polydiorganosiloxane copolymer having a purity (degree of purification) of 100%.

[0102] (Component B: (meth)acrylic modified polyorganosiloxane) The resin composition of the present invention contains a (meth)acrylic-modified polyorganosiloxane as component B. The (meth)acrylic-modified polyorganosiloxane is also called a silicone-modified (meth)acrylic polymer. The present inventors conducted a detailed analysis of the black discoloration and poor appearance caused by black spots in a specific PC-POS copolymer, and found that the components contained in the PC-POS copolymer exhibit adhesion when melted in a molding machine, and scrape off the carbonized layer and corroded metal attached to the inner wall and screw of the molding machine. As a result of intensive research to solve this problem, it was found for the first time that the (meth)acrylic-modified polyorganosiloxane has the effect of weakening the adhesion of the PC-POS copolymer or forming a lubricant layer on the inner wall and cylinder of the molding machine, and has the effect of suppressing the black discoloration and poor appearance caused by black spots. Note that when a polyorganosiloxane or a (meth)acrylic resin that is not (meth)acrylic-modified is used as component B, there is no effect of suppressing the black discoloration and poor appearance caused by black spots.

[0103] The (meth)acrylic-modified polyorganosiloxane in the present invention is preferably a (meth)acrylic-modified polyorganosiloxane obtained by graft copolymerizing a (meth)acrylic acid ester (component B2) with a polyorganosiloxane (component B1) represented by the following general formula [4]:

[0104] [ka]

[0105] [In the above general formula [4], R 1 , R 2 and R 3each independently represents a hydrocarbon group having 1 to 20 carbon atoms or a halogenated hydrocarbon group having 1 to 20 carbon atoms, and Y represents an organic group having at least one group selected from the group consisting of a radical reactive group selected from the group consisting of a vinyl group, an allyl group, and a γ-(meth)acryloxypropyl group, and an SH group. 1 and X 2 each independently represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or SiR 4 R 5 R 6 (R 4 , R 5 each independently represents a hydrocarbon group having 1 to 20 carbon atoms or a halogenated hydrocarbon group having 1 to 20 carbon atoms; R 6 represents an organic group having at least one group selected from the group consisting of a hydrocarbon group having 1 to 20 carbon atoms, a halogenated hydrocarbon group having 1 to 20 carbon atoms, or a radical reactive group selected from the group consisting of a vinyl group, an allyl group, and a γ-(meth)acryloxypropyl group, and an SH group), m is an integer of 1 to 10,000, n is an integer of 1 or more, and the siloxane chain may be branched.]

[0106] In the above general formula [4], R 1 , R 2 and R 3 are preferably each independently a hydrocarbon group having 1 to 10 carbon atoms, and more preferably a methyl group.

[0107] Such (meth)acrylic modified polyorganosiloxanes can be produced by known methods. For example, they can be produced by combining hydrolysis, polymerization, and equilibration means using linear or cyclic low molecular weight polyorganosiloxanes or alkoxysilanes having the above groups. Hydrolysis, polymerization, and equilibration can be carried out by known techniques even in a state dispersed in water.

[0108] The B2 component is an alkyl ester, hydroxyalkyl ester, or alkoxyalkyl ester of acrylic acid or methacrylic acid, and specifically includes acrylic acid esters such as methyl acrylate, ethyl acrylate, isopropyl acrylate, n-propyl acrylate, n-butyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate, isooctyl acrylate, n-octyl acrylate, 2-hydroxyethyl acrylate, and 2-methoxyethyl acrylate, and methacrylic acid esters such as methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, n-propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, n-lauryl methacrylate, 2-hydroxyethyl methacrylate, and 2-ethoxyethyl methacrylate. These can be used alone or in combination of two or more, and in particular, methyl methacrylate and 2-hydroxyethyl methacrylate are preferred.

[0109] In addition, other monomers copolymerizable with (meth)acrylic acid esters may be included. As representative examples of such monomers, there may be mentioned styrene-based compounds such as styrene, vinyl toluene, and α-methylstyrene, unsaturated nitriles such as acrylonitrile and methacrylonitrile, halogenated olefins such as vinyl chloride and vinylidene chloride, vinyl esters such as vinyl acetate and vinyl propionate, unsaturated amides such as acrylamide, methacrylamide, and N-methylolacrylamide, unsaturated carboxylic acids such as acrylic acid, methacrylic acid, and maleic anhydride, and other monomers having one double bond, as well as polyunsaturated monomers such as ethylene glycol dimethacrylate, propylene glycol dimethacrylate, 1,4-butanediol dimethacrylate, allyl methacrylate, triallyl cyanurate, and triallyl isocyanurate. Two or more of these may be used.

[0110] The content of these other copolymerizable monomers is preferably 30% by weight or less, more preferably 25% by weight or less, and even more preferably 20% by weight or less, based on 100% by weight of the total amount with the (meth)acrylic acid ester.

[0111] The graft copolymerization can be carried out by a known technique. For example, the polyorganosiloxane and the (meth)acrylic acid ester or a mixture of the polyorganosiloxane and other monomers are emulsified and dispersed in water, and polymerized in the presence of a radical polymerization initiator to carry out the graft copolymerization. The emulsifier and radical polymerization initiator used in this method may be known for emulsion polymerization. After the polymerization is completed, the graft copolymer can be obtained by salting out, filtering, washing with water, and drying. In this emulsion graft copolymerization, if the polyorganosiloxane is produced in a dispersed state in water as described above, the obtained emulsion of polyorganosiloxane can be used as it is as a raw material for graft copolymerization.

[0112] The (meth)acrylic modified polyorganosiloxane of the present invention is a graft copolymer of polyorganosiloxane (B1 component) and (meth)acrylic acid ester (B2 component) at a weight ratio of B1 component / B2 component of preferably 95 / 5 to 5 / 95, more preferably 90 / 10 to 20 / 80, further preferably 85 / 15 to 30 / 70, and particularly preferably 80 / 20 to 40 / 60. In this weight ratio, if the polyorganosiloxane exceeds 95 parts by weight, the compatibility with polycarbonate may be insufficient, resulting in poor mechanical strength, and if it is less than 5 parts by weight, the occurrence of black discoloration and poor appearance due to black spots may not be suppressed.

[0113] As an example of the acrylic modified polyorganosiloxane in the present invention, "Nissin Chemical Industry Co., Ltd. Common examples include "Chaline (trade name)" manufactured by Toa Gosei Co., Ltd., "Simac (trade name)" manufactured by Shin-Etsu Chemical Co., Ltd., "KP-578, KP-561P, KP-562P, etc. manufactured by Shin-Etsu Chemical Co., Ltd., "8BS" manufactured by Taisei Fine Chemical Co., Ltd., and "Zemlac (trade name) and Silyl (trade name)" manufactured by Kaneka Corporation.

[0114] The content of component B is 0.3 to 2.5 parts by weight, preferably 0.5 to 1.5 parts by weight, and more preferably 0.8 to 1.2 parts by weight, relative to 100 parts by weight of component A. If the content is less than 0.3 parts by weight, the occurrence of black discoloration and poor appearance due to black spots cannot be prevented, and if it exceeds 2.5 parts by weight, poor marbled appearance and surface peeling occur.

[0115] (Component C: flame retardant) The resin composition of the present invention may contain a flame retardant. As the flame retardant, various compounds known as flame retardants for thermoplastic resins, particularly aromatic polycarbonate resins, can be used, but more preferably, (i) organic metal salt-based flame retardants (e.g., organic sulfonic acid alkali (earth) metal salts, boric acid metal salt-based flame retardants, and stannic acid metal salt-based flame retardants, etc., (ii) organic phosphorus-based flame retardants (e.g., monophosphate compounds, phosphate oligomer compounds, phosphonate oligomer compounds, phosphonitrile oligomer compounds, and phosphonic acid amide compounds, etc.), and (iii) silicone-based flame retardants made of silicone compounds. The incorporation of compounds used as flame retardants not only improves flame retardancy, but also improves, for example, antistatic properties, fluidity, rigidity, and thermal stability based on the properties of each compound.

[0116] The content of component C is preferably 0.001 to 20 parts by weight, more preferably 0.01 to 15 parts by weight, and even more preferably 0.05 to 10 parts by weight, relative to 100 parts by weight of component A. If the content of component C is less than 0.001 part by weight, flame retardancy may not be maintained, and if it exceeds 20 parts by weight, impact resistance and flame retardancy may not be satisfactory.

[0117] (Organometallic salt flame retardants) The organic metal salt flame retardant is advantageous in that it maintains heat resistance to a large extent. The organic metal salt flame retardant most advantageously used in the present invention is an alkali (earth) metal salt of sulfonate. Among them, alkali (earth) metal salts of fluorine-substituted organic sulfonic acids are preferred, and alkali (earth) metal salts of sulfonic acids having a perfluoroalkyl group are particularly preferred. Here, the carbon number of the perfluoroalkyl group is preferably in the range of 1 to 18, more preferably in the range of 1 to 10, and even more preferably in the range of 1 to 8.

[0118] The metal constituting the metal ion of the fluorine-substituted organic sulfonic acid alkali (earth) metal salt is an alkali metal or an alkaline earth metal, and examples of the alkali metal include lithium, sodium, potassium, rubidium, and cesium, and examples of the alkaline earth metal include beryllium, magnesium, calcium, strontium, and barium. More preferably, it is an alkali metal. Therefore, a suitable organic metal salt-based flame retardant is a perfluoroalkylsulfonic acid alkali metal salt. Among such alkali metals, rubidium and cesium are suitable when a higher transparency is required, but they are not versatile and difficult to purify, so that they may end up being disadvantageous in terms of cost. On the other hand, although they are advantageous in terms of cost and flame retardancy, lithium and sodium may conversely be disadvantageous in terms of transparency. Taking these into consideration, the alkali metals in the perfluoroalkylsulfonic acid alkali metal salt can be used differently, but in all respects, the most suitable is a perfluoroalkylsulfonic acid potassium salt, which has an excellent balance of properties. Such a potassium salt can also be used in combination with a perfluoroalkylsulfonic acid alkali metal salt made of another alkali metal.

[0119] Examples of such alkali metal salts of perfluoroalkylsulfonic acid include potassium trifluoromethanesulfonate, potassium perfluorobutanesulfonate, potassium perfluorohexanesulfonate, potassium perfluorooctane sulfonate, sodium pentafluoroethanesulfonate, sodium perfluorobutanesulfonate, sodium perfluorooctane sulfonate, lithium trifluoromethanesulfonate, lithium perfluorobutanesulfonate, lithium perfluoroheptanesulfonate, and trifluoromethanesulfonate. Examples of the perfluoroalkyl sulfonate include cesium perfluorobutanesulfonate, cesium perfluorooctane sulfonate, cesium perfluorohexanesulfonate, rubidium perfluorobutanesulfonate, and rubidium perfluorohexanesulfonate, and these can be used alone or in combination of two or more. Among these, potassium perfluorobutanesulfonate is particularly preferred.

[0120] The above-mentioned organometallic salt flame retardant has a fluoride ion content measured by ion chromatography of preferably 50 ppm or less, more preferably 20 ppm or less, and even more preferably 10 ppm or less. The lower the fluoride ion content, the better the flame retardancy and light resistance. The lower limit of the fluoride ion content can be substantially 0, but in consideration of the balance between the refining process and the effect, a practical value of about 0.2 ppm is preferable. A perfluoroalkylsulfonic acid alkali metal salt having such a fluoride ion content is refined, for example, as follows. A perfluoroalkylsulfonic acid alkali metal salt is dissolved in ion-exchanged water in an amount 2 to 10 times the weight of the metal salt at a temperature in the range of 40 to 90°C (more preferably 60 to 85°C). The alkali metal salt of perfluoroalkylsulfonic acid is produced by a method of neutralizing perfluoroalkylsulfonic acid with an alkali metal carbonate or hydroxide, or a method of neutralizing perfluoroalkylsulfonyl fluoride with an alkali metal carbonate or hydroxide (preferably the latter method). The ion-exchanged water is particularly preferably water having an electric resistance value of 18 MΩ·cm or more. The liquid in which the metal salt is dissolved is stirred at the above temperature for 0.1 to 3 hours, more preferably for 0.5 to 2.5 hours. Thereafter, the liquid is cooled to a range of 0 to 40°C, more preferably 10 to 35°C. Crystals are precipitated by cooling. The precipitated crystals are taken out by filtration. In this way, a suitable purified alkali metal salt of perfluoroalkylsulfonic acid is produced.

[0121] When a fluorine-substituted organic sulfonic acid alkali (earth) metal salt is used as the flame retardant, the content is preferably 0.01 to 1.0 part by weight, more preferably 0.05 to 0.8 part by weight, and even more preferably 0.08 to 0.6 part by weight, relative to 100 parts by weight of component A. When the content is within this preferred range, the effects expected from the inclusion of a fluorine-substituted organic sulfonic acid alkali (earth) metal salt (for example, flame retardancy, antistatic properties, etc.) may be exhibited.

[0122] As the organic metal salt-based flame retardant other than the fluorine-substituted organic sulfonic acid alkali (earth) metal salt, a metal salt of an organic sulfonic acid that does not contain a fluorine atom is suitable. Examples of such metal salts include an alkali metal salt of an aliphatic sulfonic acid, an alkaline earth metal salt of an aliphatic sulfonic acid, an alkali metal salt of an aromatic sulfonic acid, and an alkaline earth metal salt of an aromatic sulfonic acid (none of which contain a fluorine atom).

[0123] Preferred examples of the aliphatic sulfonic acid metal salt include alkylsulfonic acid alkali (earth) metal salts, which can be used alone or in combination of two or more (herein, the term "alkali (earth) metal salt" is used to mean both alkali metal salts and alkaline earth metal salts). Preferred examples of the alkane sulfonic acid used in such alkylsulfonic acid alkali (earth) metal salts include methanesulfonic acid, ethanesulfonic acid, propanesulfonic acid, butanesulfonic acid, methylbutanesulfonic acid, hexanesulfonic acid, heptanesulfonic acid, octanesulfonic acid, etc., which can be used alone or in combination of two or more.

[0124] The aromatic sulfonic acid used in the alkali (earth) metal salt of aromatic sulfonate may be at least one acid selected from the group consisting of monomeric or polymeric aromatic sulfide sulfonic acids, aromatic carboxylic acids and ester sulfonic acids, monomeric or polymeric aromatic ether sulfonic acids, aromatic sulfonate sulfonic acids, monomeric or polymeric aromatic sulfonic acids, monomeric or polymeric aromatic sulfone sulfonic acids, aromatic ketone sulfonic acids, heterocyclic sulfonic acids, aromatic sulfoxide sulfonic acids, and condensates of aromatic sulfonic acids with methylene bonds, and these may be used alone or in combination of two or more kinds.

[0125] Specific examples of the aromatic sulfonic acid alkali (earth) metal salts include disodium diphenyl sulfide-4,4'-disulfonate, dipotassium diphenyl sulfide-4,4'-disulfonate, potassium 5-sulfoisophthalate, sodium 5-sulfoisophthalate, polysodium polyethylene terephthalate polysulfonate, calcium 1-methoxynaphthalene-4-sulfonate, disodium 4-dodecylphenyl ether disulfonate, polysodium poly(2,6-dimethylphenylene oxide) polysulfonate, polysodium poly(1,3-phenylene oxide) polysulfonate, polysodium poly(1,4-phenylene oxide) polysulfonate, polypotassium poly(2,6-diphenylphenylene oxide) polysulfonate, lithium poly(2-fluoro-6-butylphenylene oxide) polysulfonate, potassium sulfonate of benzenesulfonate, sodium benzenesulfonate, and benzenesulfonic acid. Examples of the sulfonate include strontium, magnesium benzenesulfonate, dipotassium p-benzenedisulfonate, dipotassium naphthalene-2,6-disulfonate, calcium biphenyl-3,3'-disulfonate, sodium diphenylsulfone-3-sulfonate, potassium diphenylsulfone-3-sulfonate, dipotassium diphenylsulfone-3,3'-disulfonate, dipotassium diphenylsulfone-3,4'-disulfonate, sodium α,α,α-trifluoroacetophenone-4-sulfonate, dipotassium benzophenone-3,3'-disulfonate, disodium thiophene-2,5-disulfonate, dipotassium thiophene-2,5-disulfonate, calcium thiophene-2,5-disulfonate, sodium benzothiophenesulfonate, potassium diphenylsulfoxide-4-sulfonate, a formalin condensate of sodium naphthalenesulfonate, and a formalin condensate of sodium anthracenesulfonate.

[0126] Among the metal salts of fluorine-free organic sulfonic acids, aromatic sulfonic acid alkali (earth) metal salts are preferred, and potassium salts are particularly preferred. When such aromatic sulfonic acid alkali (earth) metal salts are used as flame retardants, the content is preferably 0.01 to 1 part by weight, more preferably 0.05 to 0.8 parts by weight, and even more preferably 0.08 to 0.6 parts by weight, per 100 parts by weight of component A.

[0127] (Organophosphorus flame retardants) As the organic phosphorus flame retardant of the present invention, a phosphate compound, particularly an aryl phosphate compound, is suitable. Such a phosphate compound is effective in improving flame retardancy, and has a plasticizing effect, so that although the heat resistance is reduced, it is advantageous in that the molding processability of the resin composition of the present invention can be improved. As such a phosphate compound, various phosphate compounds known as flame retardants can be used, but more preferably, one or more phosphate compounds represented by the following general formula [7] can be mentioned.

[0128] [ka]

[0129] [In the above general formula [7], Y is a dihydric phenol residue derived from a dihydroxy compound selected from the group consisting of hydroquinone, resorcinol, bis(4-hydroxydiphenyl)methane, bisphenol A, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3-methylcyclohexane, dihydroxydiphenyl, dihydroxynaphthalene, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)ketone, and bis(4-hydroxyphenyl)sulfide; g, h, i, and j each independently represent 0 or 1; n represents an integer of 0 to 5, or, in the case of a mixture of phosphate esters having different n's, represents the average value thereof; R 21 , R 22 , R23 , and R 24 are each independently a monohydric phenol residue derived from an aryl group selected from the group consisting of phenol, cresol, xylenol, isopropylphenol, butylphenol, and p-cumylphenol.

[0130] The phosphate compound of the above formula [7] may be a mixture of compounds having different n numbers. In the case of such a mixture, the average n number is preferably in the range of 0.5 to 1.5, more preferably 0.8 to 1.2, even more preferably 0.95 to 1.15, and particularly preferably 1 to 1.14.

[0131] Preferred specific examples of the dihydric phenol from which Y in the above formula [7] is derived include resorcinol, bisphenol A, and dihydroxydiphenyl, and among these, resorcinol and bisphenol A are preferred.

[0132] R in the above formula [7] 21 , R 22 , R 23 , and R 24 Preferred specific examples of the monohydric phenol from which the above is derived include phenol, cresol, xylenol, and 2,6-dimethylphenol, and among these, phenol and 2,6-dimethylphenol are preferred.

[0133] Specific examples of the phosphate compound of the above formula [7] include monophosphate compounds such as triphenyl phosphate and tri(2,6-xylyl)phosphate, as well as phosphate oligomers based on resorcinol bis(di(2,6-xylyl)phosphate), phosphate oligomers based on 4,4-dihydroxydiphenyl bis(diphenyl phosphate), and phosphoric ester oligomers based on bisphenol A bis(diphenyl phosphate). Of these, phosphate oligomers based on resorcinol bis(di(2,6-xylyl)phosphate), phosphate oligomers based on 4,4-dihydroxydiphenyl bis(diphenyl phosphate), and phosphoric ester oligomers based on bisphenol A bis(diphenyl phosphate) are preferred.

[0134] Another example of an organic phosphorus-based flame retardant is phosphazene. Phosphazene contains phosphorus and nitrogen atoms in the molecule, which can impart flame retardancy to a resin composition. There are no particular limitations on the phosphazene, so long as it does not contain halogen atoms and has a phosphazene structure in the molecule. The phosphazene structure here refers to a structure represented by the formula: -P(R)=N- [wherein R is an organic group]. The phosphazene compound is represented by the general formulas [8] and [9].

[0135] [ka]

[0136] [ka]

[0137] (In the above general formulas [8] and [9], R 25 , R 26 , R 27 and R 28 represents an organic group that does not contain hydrogen, a hydroxyl group, an amino group, or a halogen atom, and n represents an integer of 3 to 10.

[0138] In the above formulas [8] and [9], examples of the organic group not containing a halogen atom include an alkoxy group, a phenyl group, an amino group, and an allyl group. Among these, cyclic phenoxyphosphazenes represented by the following general formula

[10] are preferred.

[0139] [ka]

[0140] [In the above general formula

[10] , n represents an integer of 3 to 10.]

[0141] When an organic phosphorus-based flame retardant is used as the flame retardant, the content is preferably 1 to 20 parts by weight, more preferably 2 to 15 parts by weight, and further preferably 3 to 10 parts by weight, relative to 100 parts by weight of component A. If the content is within such a preferred range, the effects (e.g., flame retardancy) expected from the inclusion of the organic phosphorus-based flame retardant may be exhibited.

[0142] (Silicone compounds) The silicone compound of the present invention is not particularly limited as long as it can achieve the flame retardancy and transparency that are the objectives of the present invention, but a silicone compound having an aromatic group is preferred, and more preferably has a viscosity of 300 cSt or less at 25°C. If the viscosity is too high, the transparency of the molded product may decrease. Furthermore, in order for the silicone compound to efficiently exert its flame retardant effect, the dispersion state during the combustion process is important. Viscosity is an important factor that determines such a dispersion state. This is because the silicone compound is too easily volatilized during the combustion process. In this case, that is, in the case of a silicone compound with too low a viscosity, it is believed that it is difficult to form a uniform silicone structure during combustion because the silicone remaining in the system at the time of combustion is dilute. From this viewpoint, the viscosity at 25°C is more preferably 10 to 300 cSt, even more preferably 15 to 200 cSt, and most preferably 20 to 170 cSt.

[0143] The aromatic group of silicone compounds is bonded to silicone atoms, which contributes to improving compatibility with polycarbonate resins and maintaining transparency, and is also advantageous in forming a carbonized film during combustion, which contributes to the expression of flame retardant effects. If the compound does not have an aromatic group, it is difficult to obtain transparency in molded products, and it tends to be difficult to obtain high levels of flame retardancy.

[0144] The silicone compound of the present invention is preferably a silicone compound containing a Si-H group. In particular, it is a silicone compound containing a Si-H group and an aromatic group in the molecule, (1) the amount of Si-H groups contained (Si-H amount) is 0.1 to 1.2 mol / 100 g, (2) the proportion of aromatic groups represented by the following general formula

[11] contained (aromatic group amount) is 10 to 70% by weight,

[0145] [ka]

[0146] (In formula

[11] , X's each independently represent a hydrocarbon group having 1 to 20 carbon atoms which may have an OH group or a heteroatom-containing functional group. m1 represents an integer of 0 to 5. Furthermore, in formula

[11] , when m1 is 2 or more, each X may be different from the others.) Moreover, (3) at least one silicone compound selected from silicone compounds having an average degree of polymerization of 3 to 150 is more preferable.

[0147] More preferably, the silicone compound is at least one selected from among silicone compounds containing, as the Si-H group-containing unit, a structural unit represented by at least one of the structural units represented by the following general formulas

[12] and

[13] .

[0148] [ka]

[0149] [ka]

[0150] (In formula

[12] and formula

[13] , Z 1 ~Z 3 Each independently represents a hydrogen atom, a hydrocarbon group having 1 to 20 carbon atoms which may have a heteroatom-containing functional group, or a compound represented by the following general formula

[14] . Each of α1 to α3 independently represents 0 or 1. m2 represents an integer of 0 or 1 or more. Furthermore, in formula

[12] , when m2 is 2 or more, the repeating unit can be a plurality of repeating units which are different from each other.

[0151] [ka]

[0152] (In formula

[14] , Z 4 ~Z 8 Each independently represents a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms which may have a heteroatom-containing functional group. Each of α4 to α8 independently represents 0 or 1. m3 represents an integer of 0 or 1 or more. Furthermore, in the formula

[14] , when m3 is 2 or more, the repeating unit can be a plurality of repeating units which are different from each other. More preferably, when M is a monofunctional siloxane unit, D is a difunctional siloxane unit, and T is a trifunctional siloxane unit, the silicone compound is composed of MD units or MDT units.

[0153] The structural units Z represented by the above general formulas

[12] ,

[13] and

[14] 1 ~Z 8Examples of the hydrocarbon group having 1 to 20 carbon atoms, which may have a heteroatom-containing functional group in X of general formula

[11] , include alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, and decyl groups, cycloalkyl groups such as cyclohexyl groups, alkenyl groups such as vinyl and allyl groups, aryl groups such as phenyl and tolyl groups, and aralkyl groups, and these groups may further contain various functional groups such as epoxy groups, carboxy groups, carboxylic anhydride groups, amino groups, and mercapto groups. More preferred are alkyl groups, alkenyl groups, or aryl groups having 1 to 8 carbon atoms, and particularly preferred are alkyl groups having 1 to 4 carbon atoms such as methyl, ethyl, and propyl groups, vinyl groups, or phenyl groups.

[0154] In a silicone compound containing at least one of the structural units represented by the general formulas

[12] and

[13] , a plurality of siloxane bonds are repeated. When the copolymer has such units, they may take any of the forms of random copolymerization, block copolymerization, and tapered copolymerization.

[0155] In the present invention, it is preferable that the amount of Si-H in the silicone compound containing a preferred Si-H group is in the range of 0.1 to 1.2 mol / 100g. When the amount of Si-H is in the range of 0.1 to 1.2 mol / 100g, the formation of a silicone structure during combustion is facilitated. More preferably, the amount of Si-H is in the range of 0.1 to 1.0 mol / 100g, and most preferably in the range of 0.2 to 0.6 mol / 100g. If the amount of Si-H is small, it becomes difficult to form a silicone structure, and if the amount of Si-H is large, the thermal stability of the composition decreases. Here, the silicone structure refers to a network structure formed by the reaction between silicone compounds or the reaction between a resin and silicone.

[0156] The amount of Si-H groups referred to here refers to the number of moles of Si-H structure contained in 100g of silicone compound, which can be determined by measuring the volume of hydrogen gas generated per unit weight of silicone compound using an alkali decomposition method.For example, if 122ml of hydrogen gas is generated per 1g of silicone compound at 25°C, the amount of Si-H is calculated to be 0.5mol / 100g according to the following formula. 122×273 / (273+25)÷22400×100≒0.5

[0157] The silicone compound of the present invention preferably has an aromatic group content of 10 to 70% by weight. More preferably, the aromatic group content is in the range of 15 to 60% by weight, and most preferably in the range of 25 to 55% by weight. If the aromatic group content in the silicone compound is less than 10% by weight, the silicone compound may be unevenly distributed and poorly dispersed, resulting in poor appearance. If the aromatic group content is more than 70% by weight, the rigidity of the molecules of the silicone compound itself increases, so that the silicone compound may also be unevenly distributed and poorly dispersed, resulting in poor appearance.

[0158] The amount of aromatic groups herein refers to the proportion of aromatic groups represented by the general formula

[11] in the silicone compound, and can be calculated by the following formula: Aromatic group amount = [A / M] × 100 (weight%) Here, A and M in the above formula respectively represent the following values. A = the total molecular weight of all aromatic groups represented by the general formula

[11] contained in one molecule of the silicone compound M = molecular weight of silicone compound

[0159] Furthermore, the silicone compound used in the present invention desirably has a refractive index at 25° C. in the range of 1.40 to 1.60. More preferably, the silicone compound has a refractive index in the range of 1.42 to 1.59, and most preferably in the range of 1.44 to 1.59. When the refractive index is within the above range, the silicone compound is finely dispersed in the aromatic polycarbonate, thereby providing a resin composition with less cloudiness and good dyeability.

[0160] Furthermore, the silicone compound used in the present invention preferably has a volatilization amount of 18% or less as measured by a heat loss method at 105°C for 3 hours. More preferably, the silicone compound has a volatilization amount of 10% or less. If the volatilization amount is more than 18%, there will be a problem that the amount of volatile matter from the resin will be large when the resin composition of the present invention is extruded and pelletized, and there will also be a problem that the amount of bubbles generated in the molded product will be large.

[0161] The silicone compound to be used is linear as long as it satisfies the above conditions. The structure may be either a straight or branched structure, and various compounds having Si-H groups at any one of a side chain, a terminal, a branch point, or at multiple sites in the molecular structure can be used.

[0162] Generally, the structure of a silicone compound containing Si-H groups in the molecule is composed of any combination of the four types of siloxane units shown below.

[0163] M units: (CH3)3SiO 1 / 2 , H(CH3)2SiO 1 / 2 , H2(CH3)SiO 1 / 2 , (CH3)2(CH2=CH)SiO 1 / 2 , (CH3)2(C6H5)SiO 1 / 2 , (CH3)(C6H5)(CH2=CH)SiO 1 / 2 Monofunctional siloxane units such as D unit: bifunctional siloxane unit such as (CH3)2SiO, H(CH3)SiO, H2SiO, H(C6H5)SiO, (CH3)(CH2=CH)SiO, (C6H5)2SiO, etc. T units: (CH3)SiO 3 / 2 , (C3H7)SiO 3 / 2 , HSiO 3 / 2 , (CH2=CH)SiO 3 / 2 , (C6H5)SiO 3 / 2 Trifunctional siloxane units such as Q unit: tetrafunctional siloxane unit represented by SiO2

[0164] The structure of the silicone compound containing Si-H groups used in the present invention is specifically represented by the rational formula D n , T p , M m D n , M m T p , M m Q q , M m D n T p , M m D n Q q , M m T p Q q , M m D n T p Q q , D n T p , D n Q q , D n T p Q q Among these, the preferred structure of the silicone compound is M m D n , M m T p , M m D n T p , M m D n Q q and a more preferred structure is M m D n or M m D n Tp It is. (The coefficients m, n, p, and q in the above rational formula are integers that represent the degree of polymerization of each siloxane unit. Furthermore, when any of m, n, p, and q is a value of 2 or more, the siloxane unit with that coefficient can be two or more types of siloxane units that have different hydrocarbon groups having 1 to 20 carbon atoms that may have a bonded hydrogen atom or a heteroatom-containing functional group.)

[0165] Here, the sum of the coefficients in each rational formula is the average degree of polymerization of the silicone compound. In the present invention, the average degree of polymerization is preferably in the range of 3 to 150, more preferably in the range of 4 to 80, and further preferably in the range of 5 to 60. If the degree of polymerization is less than 3, the volatility of the silicone compound itself becomes high, so that there is a problem that the amount of volatile matter from the resin tends to increase during processing of the resin composition containing this silicone compound. If the degree of polymerization is more than 150, the flame retardancy and transparency of the resin composition containing this silicone compound tend to be insufficient. The above silicone compounds may be used alone or in combination of two or more kinds.

[0166] Such a silicone compound having a Si-H bond can be produced by a conventional method. For example, according to the structure of the desired silicone compound, the corresponding organochlorosilanes are co-hydrolyzed, and the by-product hydrochloric acid and low boiling points are removed to obtain the desired product. In addition, when silicone oils, cyclic siloxanes, and alkoxysilanes having a hydrocarbon group having 1 to 20 carbon atoms, which may have a Si-H bond or an aromatic group represented by the general formula

[10] or other heteroatom-containing functional group in the molecule, are used as starting materials, and an acid catalyst such as hydrochloric acid, sulfuric acid, or methanesulfonic acid is used, and water for hydrolysis is added in some cases to proceed with the polymerization reaction, and then the acid catalyst and low boiling points used are similarly removed to obtain the desired silicone compound.

[0167] Furthermore, the silicone compound containing Si-H groups has siloxane units M and M represented by the following structural formula: H , D, DH , D φ2 , T, T φ (where M is (CH3)3SiO 1 / 2 M H :H(CH3)2SiO 1 / 2 D: (CH3)2SiOD H :H(CH3)SiOD φ2 :(C6H5)2SiT:(CH3)SiO 3 / 2 T φ :(C6H5)SiO 3 / 2 ), and the average number of each siloxane unit per molecule is m and m h , d, d h , d p2 , t, t p In this case, it is preferable that all of the following relations are satisfied. 2 ≦ m+m h <= 40 0.35 ≦ d+d h +d p2 <= 148 0 ≦ t+t p <= 38 0.35 ≦ m h +d h <= 110 Outside this range, it becomes difficult to simultaneously achieve good flame retardancy and excellent transparency in the resin composition of the present invention, and in some cases, it becomes difficult to produce the silicone compound containing Si-H groups.

[0168] The content of the silicone compound used in the present invention is preferably 0.1 to 7 parts by weight, more preferably 0.1 to 4 parts by weight, further preferably 0.1 to 2 parts by weight, and particularly preferably 0.1 to 1 part by weight, based on 100 parts by weight of component A. If the content is too high, the heat resistance of the resin may decrease and gas may be easily generated during processing, while if the content is too low, flame retardancy may not be exhibited.

[0169] (Component D: Fluorine-containing drip prevention agent) The resin composition of the present invention may contain a fluorine-containing drip-preventing agent. By containing this fluorine-containing drip-preventing agent, good flame retardancy can be achieved without impairing the physical properties of the molded article.

[0170] Examples of the fluorine-containing drip prevention agent include fluorine-containing polymers having fibril-forming ability, and examples of such polymers include polytetrafluoroethylene, tetrafluoroethylene copolymers (e.g., tetrafluoroethylene / hexafluoropropylene copolymers, etc.), partially fluorinated polymers as shown in U.S. Patent No. 4,379,910, polycarbonate resins produced from fluorinated diphenols, etc. Among these, polytetrafluoroethylene (hereinafter sometimes referred to as PTFE) is preferred.

[0171] The molecular weight of the fibril-forming PTFE is extremely high, and it shows a tendency to bond PTFE to each other and become fibrous by external action such as shear force. The molecular weight is 1 million to 10 million, more preferably 2 million to 9 million, in terms of number average molecular weight calculated from the standard specific gravity. Such PTFE can be used in the form of a solid or an aqueous dispersion. In addition, such fibril-forming PTFE can be used in the form of a PTFE mixture mixed with other resins to improve dispersibility in resins and obtain better flame retardancy and mechanical properties.

[0172] Commercially available PTFE products having such fibril-forming ability include, for example, Teflon (registered trademark) 6J from Mitsui DuPont Fluorochemicals Co., Ltd. and Polyflon MPA from Daikin Industries, Ltd. Representative examples of commercially available aqueous dispersions of PTFE include Fluon AD-1 and AD-936 manufactured by Asahi ICI Fluoropolymers Co., Ltd., Fluon D-1 and D-2 manufactured by Daikin Industries, Ltd., and Teflon (registered trademark) 30J manufactured by DuPont-Mitsui Fluorochemicals Co., Ltd.

[0173] Examples of the mixed form of PTFE include: (1) a method in which an aqueous dispersion of PTFE is mixed with an aqueous dispersion or solution of an organic polymer and co-precipitated to obtain a co-aggregated mixture (methods described in JP-A-60-258263, JP-A-63-154744, etc.); (2) a method in which an aqueous dispersion of PTFE is mixed with dried organic polymer particles (method described in JP-A-4-272957); and (3) a method in which an aqueous dispersion of PTFE is uniformly mixed with an organic polymer particle solution and the respective media are simultaneously removed from the mixture (method described in JP-A-06-220210). (4) a method of polymerizing a monomer that forms an organic polymer in an aqueous dispersion of PTFE (method described in JP-A-09-95583), and (5) a method of uniformly mixing an aqueous dispersion of PTFE and an organic polymer dispersion, polymerizing a vinyl monomer in the mixed dispersion, and then obtaining a mixture (method described in JP-A-11-29679). Commercially available PTFE mixtures include "Metablen A3800" (trade name) manufactured by Mitsubishi Rayon Co., Ltd., and "BLENDEX B449" (trade name) manufactured by GE Specialty Chemicals.

[0174] The proportion of PTFE in the mixed form is preferably 1 to 60% by weight, more preferably 5 to 55% by weight, in 100% by weight of the PTFE mixture. When the proportion of PTFE is within this range, good dispersibility of PTFE can be achieved. The proportion of the above D component indicates the net amount of the drip prevention agent, and in the case of the mixed form PTFE, indicates the net amount of PTFE.

[0175] The content of component D is preferably 0.01 to 5 parts by weight, more preferably 0.05 to 1.5 parts by weight, and even more preferably 0.1 to 1 part by weight, relative to 100 parts by weight of component A. If the content of component D is less than 0.01 part by weight, the flame retardancy may be insufficient, and if it exceeds 5 parts by weight, PTFE may precipitate on the surface of the molded article, resulting in poor appearance, and may also lead to an increase in the cost of the resin composition.

[0176] (Other additives) The resin composition of the present invention preferably contains the following additives according to the intended use. (i) Phosphorus-based stabilizers Examples of phosphorus-based stabilizers include phosphorous acid, phosphoric acid, phosphonous acid, phosphonic acid and their esters, and tertiary phosphines.

[0177] Specific examples of the phosphite compound include triphenyl phosphite, tris(nonylphenyl)phosphite, tridecyl phosphite, trioctyl phosphite, trioctadecyl phosphite, didecyl monophenyl phosphite, dioctyl monophenyl phosphite, diisopropyl monophenyl phosphite, monobutyl diphenyl phosphite, monodecyl diphenyl phosphite, monooctyl diphenyl phosphite, tris(diethylphenyl)phosphite, tris(di-iso-propylphenyl)phosphite, tris(di-n-butylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, tris(2,6-di-tert-butylphenyl)phosphite, butylphenyl)phosphite, distearyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-ethylphenyl)pentaerythritol diphosphite, bis{2,4-bis(1-methyl-1-phenylethyl)phenyl}pentaerythritol diphosphite, phenyl bisphenol A pentaerythritol diphosphite, bis(nonylphenyl)pentaerythritol diphosphite, and dicyclohexyl pentaerythritol diphosphite.

[0178] Further, other phosphite compounds that react with dihydric phenols to form a cyclic structure can also be used. For example, 2,2'-methylenebis(4,6-di-tert-butylphenyl)(2,4-di-tert-butylphenyl)phosphite, 2,2'-methylenebis(4,6-di-tert-butylphenyl)(2-tert-butyl-4-methylphenyl)phosphite, and 2,2-methylenebis(4,6-di-tert-butylphenyl) octyl phosphite, etc.

[0179] Examples of the phosphate compound include tributyl phosphate, trimethyl phosphate, tricresyl phosphate, triphenyl phosphate, trichlorophenyl phosphate, triethyl phosphate, diphenyl cresyl phosphate, diphenyl monoorthoxenyl phosphate, tributoxyethyl phosphate, dibutyl phosphate, dioctyl phosphate, diisopropyl phosphate, and the like, and preferably triphenyl phosphate and trimethyl phosphate.

[0180] Examples of the phosphonite compounds include tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite, tetrakis(2,4-di-tert-butylphenyl)-4,3'-biphenylene diphosphonite, tetrakis(2,4-di-tert-butylphenyl)-3,3'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-4,3'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-3,3'-biphenylene diphosphonite, bis(2,4-di-tert-butylphenyl)-4-phenyl-phenylphosphonite, bis Examples of the phosphonite include (2,4-di-tert-butylphenyl)-3-phenyl-phenylphosphonite, bis(2,6-di-n-butylphenyl)-3-phenyl-phenylphosphonite, bis(2,6-di-tert-butylphenyl)-4-phenyl-phenylphosphonite, and bis(2,6-di-tert-butylphenyl)-3-phenyl-phenylphosphonite. Tetrakis(di-tert-butylphenyl)-biphenylene diphosphonite and bis(di-tert-butylphenyl)-phenyl-phenylphosphonite are preferred, and tetrakis(2,4-di-tert-butylphenyl)-biphenylene diphosphonite and bis(2,4-di-tert-butylphenyl)-phenyl-phenylphosphonite are more preferred. Such phosphonite compounds can be used in combination with the phosphite compounds having an aryl group substituted with two or more alkyl groups, and are therefore preferred.

[0181] Examples of the phosphonate compound include dimethyl benzenephosphonate, diethyl benzenephosphonate, and dipropyl benzenephosphonate.

[0182] Examples of tertiary phosphines include triethylphosphine, tripropylphosphine, tributylphosphine, trioctylphosphine, triamylphosphine, dimethylphenylphosphine, dibutylphenylphosphine, diphenylmethylphosphine, diphenyloctylphosphine, triphenylphosphine, tri-p-tolylphosphine, trinaphthylphosphine, and diphenylbenzylphosphine. A particularly preferred tertiary phosphine is triphenylphosphine.

[0183] The phosphorus-based stabilizers may be used alone or in combination of two or more. Among the phosphorus-based stabilizers, phosphonite compounds or phosphite compounds represented by the following general formula

[15] are preferred.

[0184] [ka]

[0185] (In the above general formula

[15] , R and R' are each an alkyl group having 6 to 30 carbon atoms or They may be the same or different.)

[0186] As described above, the phosphonite compound is preferably tetrakis(2,4-di-tert-butylphenyl)-biphenylene diphosphonite, and stabilizers containing this phosphonite as a main component are commercially available as Sandostab P-EPQ (trademark, manufactured by Clariant) and Irgafos P-EPQ (trademark, manufactured by CIBA SPECIALTY CHEMICALS), either of which can be used.

[0187] Among the above formula

[15] , more suitable phosphite compounds are distearyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, and bis{2,4-bis(1-methyl-1-phenylethyl)phenyl}pentaerythritol diphosphite.

[0188] Distearyl pentaerythritol diphosphite is commercially available as ADK STAB PEP-8 (trademark, manufactured by Asahi Denka Kogyo Co., Ltd.) and JPP681S (trademark, manufactured by Johoku Chemical Industry Co., Ltd.), and any of these can be used. Bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite is commercially available as ADK STAB PEP-24G (trademark, manufactured by Asahi Denka Kogyo Co., Ltd.), Alkanox P-24 (trademark, manufactured by Great Lakes), Ultranox P626 (trademark, manufactured by GE Specialty Chemicals), Doverphos S-9432 (trademark, manufactured by Dover Chemical), and Irgaofos 126 and 126FF (trademarks, manufactured by CIBA SPECIALTY CHEMICALS), and any of these can be used. Bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite is commercially available as ADK STAB PEP-36 (trademark, manufactured by Asahi Denka Kogyo Co., Ltd.) and can be easily used. Bis{2,4-bis(1-methyl-1-phenylethyl)phenyl}pentaerythritol diphosphite is commercially available as ADK STAB PEP-45 (trademark, manufactured by Asahi Denka Kogyo Co., Ltd.) and Doverphos S-9228 (trademark, manufactured by Dover Chemical Co., Ltd.), and either can be used.

[0189] (ii) Hindered phenol antioxidants As the hindered phenol compound, various compounds that are usually blended in resins can be used. Examples of such hindered phenol compounds include α-tocopherol, butyl hydroxytoluene, sinapyl alcohol, vitamin E, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2-tert-butyl-6-(3'-tert-butyl-5'-methyl-2'-hydroxybenzyl)-4-methylphenyl acrylate, 2,6-di-tert-butyl-4-(N,N-dimethylaminomethyl)phenol, 3,5-di-tert-butyl-4-hydroxybenzyl Phosphonate diethyl ester, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-methylenebis(2,6-di-tert-butylphenol), 2,2'-methylenebis(4-methyl-6-cyclohexylphenol), 2,2'-dimethylene-bis(6-α-methyl-benzyl-p-cresol), 2,2'-ethylidene-bis(4,6-di-tert-butylphenol), 2,2'-butylidene-bis(4 -methyl-6-tert-butylphenol), 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), triethylene glycol-N-bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate, 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], bis[2-tert-butyl-4-methyl-6-(3-tert-butyl-5-methyl-2-hydroxybenzyl)phenyl]terephthalate, 3,9- Bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1,-dimethylethyl}-2,4,8,10-tetraoxaspiro[5,5]undecane, 4,4'-thiobis(6-tert-butyl-m-cresol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), 2,2'-thiobis(4-methyl-6-tert-butylphenol), bis(3,5-di-tert-butyl-4-hydroxybenzyl)sulfide, 4,4'-dithiobis(2,6-di-tert-butylphenol), 4,4'-tri-thiobis(2,6-di-tert-butylphenol), 2,2-thiodiethylene bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,4-bis(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylanilino)-1,3,5-triazine, N,N'-hexamethylene bis-(3,5-di-tert-butyl-4-hydroxyhydrocinnamide), N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tris(3,5-di-tert-butyl-4-hydroxyphenyl)isocyanurate, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanurate 1,3,5-tris-2[3(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy]ethyl isocyanurate, tetrakis[methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]methane, triethylene glycol-N-bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate, triethylene glycol-N-bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)acetate, 3,9-bis[2-{3- (3-tert-butyl-4-hydroxy-5-methylphenyl)acetyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane, tetrakis[methylene-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate]methane, 1,3,5-trimethyl-2,4,6-tris(3-tert-butyl-4-hydroxy-5-methylbenzyl)benzene, and tris(3-tert-butyl-4-hydroxy-5-methylbenzyl)isocyanurate are examples.

[0190] Among the above compounds, tetrakis[methylene-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate]methane, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 3,9-bis[2-{3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane are preferably used in the present invention. In particular, 3,9-bis[2-{3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane is preferred. The above hindered phenol-based antioxidants can be used alone or in combination of two or more.

[0191] It is preferable that either the phosphorus-based stabilizer or the hindered phenol-based antioxidant is contained, and it is more preferable that they are used in combination. The content of the phosphorus-based stabilizer and the hindered phenol-based antioxidant is preferably 0.001 to 3 parts by weight, more preferably 0.005 to 2 parts by weight, and even more preferably 0.01 to 1 part by weight, per 100 parts by weight of the A component. In the case of a combination, it is more preferable that 0.01 to 0.3 parts by weight of the phosphorus-based stabilizer and 0.01 to 0.3 parts by weight of the hindered phenol-based antioxidant are contained per 100 parts by weight of the A component.

[0192] (iii) Other heat stabilizers The resin composition of the present invention may contain other heat stabilizers than the phosphorus-based stabilizer and the hindered phenol-based antioxidant. Such other heat stabilizers are preferably used in combination with either one of these stabilizers and antioxidants, and particularly preferably used in combination with both. Suitable examples of such other heat stabilizers include lactone-based stabilizers such as the reaction product of 3-hydroxy-5,7-di-tert-butyl-furan-2-one and o-xylene (details of such stabilizers are described in JP-A-7-233160). Such a compound is commercially available as Irganox HP-136 (trademark, manufactured by CIBA SPECIALTY CHEMICALS), and this compound can be used. Furthermore, stabilizers in which this compound is mixed with various phosphite compounds and hindered phenol compounds are commercially available. Suitable examples include Irganox HP-2921 manufactured by the above company. Such premixed stabilizers can also be used in the present invention. The amount of the lactone-based stabilizer to be added is preferably 0.0005 to 0.05 parts by weight, and more preferably 0.001 to 0.03 parts by weight, per 100 parts by weight of the A component.

[0193] Other examples of the stabilizer include sulfur-containing stabilizers such as pentaerythritol tetrakis (3-mercaptopropionate), pentaerythritol tetrakis (3-laurylthiopropionate), and glycerol-3-stearylthiopropionate. Such stabilizers are particularly effective when the resin composition is applied to rotational molding. The content of such sulfur-containing stabilizers is preferably 0.001 to 0.1 parts by weight, more preferably 0.01 to 0.08 parts by weight, based on 100 parts by weight of component A.

[0194] (iv) Mold release agent The polycarbonate resin composition of the present invention preferably further contains a mold release agent for the purpose of improving the productivity during molding and reducing distortion of the molded product. As such a mold release agent, a known one can be used. For example, saturated fatty acid esters, unsaturated fatty acid esters, polyolefin waxes (polyethylene wax, 1-alkene polymers, etc., those modified with functional group-containing compounds such as acid modification can also be used), silicone compounds, fluorine compounds (fluorine oils represented by polyfluoroalkyl ethers, etc.), paraffin wax, beeswax, etc. can be mentioned. Among them, fatty acid esters can be mentioned as a preferred mold release agent. Such fatty acid esters are esters of aliphatic alcohols and aliphatic carboxylic acids. Such aliphatic alcohols may be monohydric alcohols or polyhydric alcohols having dihydric or higher valences. The carbon number of the alcohol is in the range of 3 to 32, more preferably in the range of 5 to 30. Examples of such monohydric alcohols include dodecanol, tetradecanol, hexadecanol, octadecanol, eicosanol, tetracosanol, ceryl alcohol, and triacontanol. Examples of such polyhydric alcohols include pentaerythritol, dipentaerythritol, tripentaerythritol, polyglycerol (triglycerol to hexaglycerol), ditrimethylolpropane, xylitol, sorbitol, and mannitol. In the fatty acid ester of the present invention, polyhydric alcohols are more preferred.

[0195] On the other hand, the aliphatic carboxylic acid preferably has 3 to 32 carbon atoms, and particularly preferably has 10 to 22 carbon atoms. Examples of the aliphatic carboxylic acid include saturated aliphatic carboxylic acids such as decanoic acid, undecanoic acid, dodecanoic acid, tridecanoic acid, tetradecanoic acid, pentadecanoic acid, hexadecanoic acid (palmitic acid), heptadecanoic acid, octadecanoic acid (stearic acid), nonadecanoic acid, behenic acid, icosanoic acid, and docosanoic acid, and unsaturated aliphatic carboxylic acids such as palmitoleic acid, oleic acid, linoleic acid, linolenic acid, eicosenoic acid, eicosapentaenoic acid, and cetoleic acid. Among the above, the aliphatic carboxylic acid is preferably one having 14 to 20 carbon atoms. Among them, saturated aliphatic carboxylic acids are preferred. Stearic acid and palmitic acid are particularly preferred.

[0196] The above-mentioned aliphatic carboxylic acids such as stearic acid and palmitic acid are usually produced from natural oils and fats such as animal oils and fats such as beef tallow and lard, and vegetable oils and fats such as palm oil and sunflower oil, and therefore these aliphatic carboxylic acids are usually mixtures containing other carboxylic acid components with different numbers of carbon atoms. Therefore, in the production of the fatty acid ester of the present invention, aliphatic carboxylic acids produced from such natural oils and fats and in the form of a mixture containing other carboxylic acid components, particularly stearic acid and palmitic acid, are preferably used.

[0197] The fatty acid ester of the present invention may be either a partial ester or a full ester (full ester). However, partial esters usually have a high hydroxyl value and tend to induce decomposition of the resin at high temperatures, so full esters are more preferred. The acid value of the fatty acid ester of the present invention is preferably 20 or less, more preferably in the range of 4 to 20, and even more preferably in the range of 4 to 12, from the viewpoint of thermal stability. The acid value can be substantially 0. The hydroxyl value of the fatty acid ester is more preferably in the range of 0.1 to 30. The iodine value is preferably 10 or less. The iodine value can be substantially 0. These properties can be determined by the method specified in JIS K 0070.

[0198] The content of the mold release agent is preferably 0.005 to 2 parts by weight, more preferably 0.01 to 1 part by weight, and further preferably 0.05 to 0.5 parts by weight, based on 100 parts by weight of the A component. In this range, the polycarbonate resin composition may have good mold releasability and roll releasability. In particular, such an amount of fatty acid ester provides a flame-retardant resin composition having good mold releasability and roll releasability without impairing good hue.

[0199] (v) Ultraviolet absorbers The polycarbonate resin composition of the present invention preferably contains an ultraviolet absorbing agent to suppress ultraviolet degradation in outdoor applications.Specific examples of the ultraviolet absorbing agent include benzophenone-based agents such as 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octoxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, 2-hydroxy-4-methoxy-5-sulfoxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxy-5-sodiumsulfoxybenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2-hydroxy-4-n-dodecyloxybenzophenone, and 2-hydroxy-4-methoxy-2'-carboxybenzophenone.Specific examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers such as 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-3,5-dicumylphenyl)phenylbenzotriazole, 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)-5-chlorobenzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(2-hydroxy-3,5-di-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2-hydroxy-3,5-di-tert-amylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, Examples of the copolymer include 2-hydroxyphenyl-2H-benzotriazole skeleton such as 2-(2-hydroxy-5-acryloxyethylphenyl)-2H-benzotriazole, 2-(2-hydroxy-5-tert-butylphenyl)-benzotriazole, 2-(2-hydroxy-4-octoxyphenyl)-benzotriazole, 2,2'-methylenebis(4-cumyl-6-benzotriazolephenyl), 2,2'-p-phenylenebis(1,3-benzoxazin-4-one), and 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidomethyl)-5-methylphenyl]benzotriazole, and copolymers of 2-(2'-hydroxy-5-methacryloxyethylphenyl)-2H-benzotriazole and vinyl monomers copolymerizable with the monomer, and copolymers of 2-(2'-hydroxy-5-acryloxyethylphenyl)-2H-benzotriazole and vinyl monomers copolymerizable with the monomer.Specific examples of the ultraviolet absorber include, in the hydroxyphenyltriazine series, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-hexyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-methyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-ethyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-propyloxyphenol, and 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-butyloxyphenol.Further examples include compounds in which the phenyl group of the above-mentioned compounds is a 2,4-dimethylphenyl group, such as 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-hexyloxyphenol. Specific examples of the ultraviolet absorbent include cyclic iminoesters such as 2,2'-p-phenylenebis(3,1-benzoxazine-4-one), 2,2'-m-phenylenebis(3,1-benzoxazine-4-one), and 2,2'-p,p'-diphenylenebis(3,1-benzoxazine-4-one). Specific examples of the ultraviolet absorbent include cyanoacrylates such as 1,3-bis-[(2'-cyano-3',3'-diphenylacryloyl)oxy]-2,2-bis[(2-cyano-3,3-diphenylacryloyl)oxy]methyl)propane and 1,3-bis-[(2-cyano-3,3-diphenylacryloyl)oxy]benzene. Furthermore, the ultraviolet absorber may be a polymer type ultraviolet absorber obtained by copolymerizing such an ultraviolet absorbing monomer and / or a light stable monomer with a monomer such as an alkyl (meth)acrylate by adopting a structure of a radically polymerizable monomer compound. Suitable examples of the ultraviolet absorbing monomer include compounds containing a benzotriazole skeleton, a benzophenone skeleton, a triazine skeleton, a cyclic imino ester skeleton, and a cyanoacrylate skeleton in the ester substituent of a (meth)acrylic acid ester.Among the above, benzotriazole and hydroxyphenyltriazine are preferred in terms of ultraviolet absorbing ability, and cyclic iminoester and cyanoacrylate are preferred in terms of heat resistance and color. Specific examples include "Chemisorb 79" from Chemipro Chemical Co., Ltd. and "Tinuvin 234" from BASF Japan Ltd. The ultraviolet absorbing agents may be used alone or in a mixture of two or more kinds.

[0200] The content of the ultraviolet absorber is preferably 0.01 to 3 parts by weight, more preferably 0.01 to 1 part by weight, further preferably 0.05 to 1 part by weight, and particularly preferably 0.05 to 0.5 parts by weight, based on 100 parts by weight of the resin component. If the content is less than 0.01 part by weight, the weather resistance may be insufficient, and if it exceeds 3 parts by weight, the flame retardancy may be insufficient.

[0201] (vi) Dyes and pigments The polycarbonate resin composition of the present invention further contains various dyes and pigments, and can provide molded products that exhibit a variety of designs. Examples of dyes and pigments used in the present invention include perylene dyes, coumarin dyes, thioindigo dyes, anthraquinone dyes, thioxanthone dyes, ferrocyanides such as Prussian blue, perinone dyes, quinoline dyes, quinacridone dyes, dioxazine dyes, isoindolinone dyes, and phthalocyanine dyes. Furthermore, the polycarbonate resin composition of the present invention can be blended with a metallic pigment to obtain a better metallic color. Aluminum powder is suitable as the metallic pigment. In addition, by blending a fluorescent brightener or other fluorescent dye that emits light, a better design effect that makes use of the luminous color can be imparted.

[0202] (vii) Fluorescent whitening agents In the resin composition of the present invention, the fluorescent brightener is not particularly limited as long as it is used to improve the color tone of the resin or the like to white or bluish white, and examples thereof include stilbene-based, benzimidazole-based, benzoxazole-based, naphthalimide-based, rhodamine-based, coumarin-based, and oxazine-based compounds. Specific examples include CI Fluorescent Brightener 219:1, Eastman Chemical Company's EASTOBRITE OB-1, and Showa Chemical Company's "HAKKOL PSR." Here, the fluorescent brightener has the effect of absorbing ultraviolet energy of light and radiating this energy in the visible region. The content of the fluorescent brightener is preferably 0.001 to 0.1 parts by weight, more preferably 0.001 to 0.05 parts by weight, based on 100 parts by weight of the A component. Even if the content exceeds 0.1 parts by weight, the effect of improving the color tone of the composition may be small.

[0203] (viii) Compounds capable of absorbing heat rays The polycarbonate resin composition of the present invention may contain a compound having heat absorbing ability. Suitable examples of such compounds include phthalocyanine-based near infrared absorbing agents, metal oxide-based near infrared absorbing agents such as ATO, ITO, iridium oxide, ruthenium oxide, immonium oxide, and titanium oxide, various metal compounds having excellent near infrared absorbing ability such as metal boride-based and tungsten oxide-based near infrared absorbing agents such as lanthanum boride, cerium boride, and tungsten boride, and carbon fillers. As such phthalocyanine-based near infrared absorbing agents, for example, MIR-362 manufactured by Mitsui Chemicals, Inc. is commercially available and easily available. Examples of carbon fillers include carbon black, graphite (both natural and artificial), and fullerene, and preferably carbon black and graphite. These can be used alone or in combination of two or more. The content of the phthalocyanine-based near infrared absorbing agent is preferably 0.0005 to 0.2 parts by weight, more preferably 0.0008 to 0.1 parts by weight, and even more preferably 0.001 to 0.07 parts by weight, based on 100 parts by weight of the resin component. The contents of the metal oxide-based near infrared absorbing agent, the metal boride-based near infrared absorbing agent, and the carbon filler are preferably in the range of 0.1 to 200 ppm (weight ratio), and more preferably in the range of 0.5 to 100 ppm, in the polycarbonate resin composition of the present invention.

[0204] (ix) Light diffusing agent The polycarbonate resin composition of the present invention can contain a light diffusing agent to impart a light diffusing effect. Examples of such light diffusing agents include polymer fine particles, inorganic fine particles with a low refractive index such as calcium carbonate, and composites thereof. Such polymer fine particles are fine particles already known as light diffusing agents for polycarbonate resins. More preferred examples include acrylic crosslinked particles with a particle size of several μm and silicone crosslinked particles represented by polyorganosilsesquioxane. Examples of the shape of the light diffusing agent include spherical, discoid, columnar, and amorphous shapes. Such a sphere does not need to be a perfect sphere and includes deformed ones, and such a columnar shape includes a cube. A preferred light diffusing agent is spherical, and the more uniform the particle size, the more preferred it is. The content of the light diffusing agent is preferably 0.005 to 20 parts by weight, more preferably 0.01 to 10 parts by weight, and even more preferably 0.01 to 3 parts by weight, relative to 100 parts by weight of component A. Two or more types of light diffusing agents can be used in combination.

[0205] (x) Highly light-reflective white pigment The polycarbonate resin composition of the present invention can contain a highly light-reflective white pigment to impart a light-reflecting effect. Titanium dioxide (particularly titanium dioxide treated with an organic surface treatment agent such as silicone) pigment is particularly preferred as such a white pigment. The content of such highly light-reflective white pigment is preferably 3 to 30 parts by weight, more preferably 8 to 25 parts by weight, per 100 parts by weight of component A. Two or more types of highly light-reflective white pigments can be used in combination.

[0206] (xi) Antistatic agents The polycarbonate resin composition of the present invention may require antistatic performance, and in such a case, it is preferable to include an antistatic agent. Examples of such antistatic agents include (1) organic sulfonate phosphonium salts such as arylsulfonate phosphonium salts, typified by dodecylbenzenesulfonate phosphonium salts, and alkylsulfonate phosphonium salts, as well as borate phosphonium salts such as tetrafluoroborate phosphonium salts. The content of the phosphonium salt is appropriately 5 parts by weight or less, preferably 0.05 to 5 parts by weight, more preferably 1 to 3.5 parts by weight, and even more preferably 1.5 to 3 parts by weight, relative to 100 parts by weight of the resin component. Examples of the antistatic agent include (2) organic sulfonate alkali (earth) metal salts such as lithium organic sulfonate, sodium organic sulfonate, potassium organic sulfonate, cesium organic sulfonate, rubidium organic sulfonate, calcium organic sulfonate, magnesium organic sulfonate, and barium organic sulfonate. As mentioned above, such metal salts are also used as flame retardants. More specifically, such metal salts include metal salts of dodecylbenzenesulfonic acid and metal salts of perfluoroalkanesulfonic acid. The content of the alkali (earth) metal salt of organic sulfonic acid is suitably 0.5 parts by weight or less, preferably 0.001 to 0.3 parts by weight, and more preferably 0.005 to 0.2 parts by weight, per 100 parts by weight of component A. In particular, alkali metal salts such as potassium, cesium, and rubidium are suitable.

[0207] Examples of the antistatic agent include (3) organic ammonium sulfonates such as ammonium alkylsulfonates and ammonium arylsulfonates. The amount of the ammonium salt is preferably 0.05 parts by weight or less based on 100 parts by weight of the resin component. Examples of the antistatic agent include (4) polymers containing a poly(oxyalkylene) glycol component as a constituent component, such as polyether ester amide. The amount of the polymer is preferably 5 parts by weight or less based on 100 parts by weight of the resin component.

[0208] (xii) Filler The polycarbonate resin composition of the present invention can contain various fillers known as reinforcing fillers. As such fillers, various fibrous fillers, plate-like fillers, and granular fillers can be used. Here, the fibrous filler is a filler having a fibrous shape (including rod-like, needle-like, or a shape in which the axis extends in multiple directions), and the plate-like filler is a filler having a plate-like shape (including a filler having an uneven surface or a filler having a curved plate). The granular filler is a filler having a shape other than these, including an indefinite shape. The above-mentioned fibrous or plate-like shapes are often clear from observation of the shape of the filler, but for example, as a difference from the so-called indefinite shape, a filler having an aspect ratio of 3 or more can be said to be fibrous or plate-like.

[0209] Preferred examples of the plate-like filler include glass flakes, talc, mica, kaolin, metal flakes, carbon flakes, and graphite, as well as plate-like fillers obtained by surface-coating these fillers with different materials such as metals and metal oxides. The particle size is preferably in the range of 0.1 to 300 μm. The particle size refers to the value of the median diameter (D50) of the particle size distribution measured by the X-ray transmission method, which is one of the liquid phase precipitation methods, in the region up to about 10 μm, the value of the median diameter (D50) of the particle size distribution measured by the laser diffraction / scattering method in the region of 10 to 50 μm, and the value of the vibration sieving method in the region of 50 to 300 μm. The particle size is the particle size in the resin composition. The plate-like filler may be surface-treated with various coupling agents such as silane-, titanate-, aluminate-, and zirconate-based coupling agents, or may be in the form of granules that have been bundled or compressed with various resins such as olefin-, styrene-, acrylic-, polyester-, epoxy-, and urethane-based resins, or higher fatty acid esters.

[0210] The fiber diameter of the fibrous filler is preferably in the range of 0.1 to 20 μm. 3 μm is more preferable, and 10 μm is even more preferable. Meanwhile, the lower limit of the fiber diameter is preferably 1 μm. The fiber diameter here refers to the number average fiber diameter. The number average fiber diameter is a value calculated from an image obtained by observing, with a scanning electron microscope, the residue collected after dissolving the molded product in a solvent or decomposing the resin with a basic compound, and the ashing residue collected after ashing in a crucible. Examples of such fibrous fillers include glass fibers, flat cross-section glass fibers, milled glass fibers, carbon fibers, milled carbon fibers, metal fibers, asbestos, rock wool, ceramic fibers, slag fibers, potassium titanate whiskers, boron whiskers, aluminum borate whiskers, calcium carbonate whiskers, titanium oxide whiskers, wollastonite, xonotlite, palygorskite (attapulgite), and sepiolite, and other fibrous inorganic fillers, typified by heat-resistant organic fibers such as aramid fibers, polyimide fibers, and polybenzothiazole fibers, as well as fibrous fillers in which the surface of these fillers is coated with a different material such as a metal or metal oxide. Examples of fillers in which a different material is coated on the surface include metal-coated glass fibers, metal-coated glass flakes, titanium oxide-coated glass flakes, and metal-coated carbon fibers. The method of surface coating of different materials is not particularly limited, and examples thereof include various known plating methods (e.g., electrolytic plating, electroless plating, hot-dip plating, etc.), vacuum deposition, ion plating, CVD (e.g., thermal CVD, MOCVD, plasma CVD, etc.), PVD, and sputtering. Here, the fibrous filler refers to a fibrous filler having an aspect ratio of 3 or more, preferably 5 or more, and more preferably 10 or more. The upper limit of the aspect ratio is about 10,000, and preferably 200. The aspect ratio of such a filler is a value in a resin composition. In addition, the flat cross-section glass fiber refers to a glass fiber having an average major axis value of the fiber cross section of 10 to 50 μm, preferably 15 to 40 μm, and more preferably 20 to 35 μm, and an average major axis / minor axis ratio (major axis / minor axis) of 1.5 to 8, preferably 2 to 6, and more preferably 2.5 to 5.The fibrous filler may be surface-treated with various coupling agents, bundled with various resins, and granulated by compression, in the same manner as the plate-like filler. The content of such a filler is preferably 200 parts by weight or less, more preferably 100 parts by weight or less, even more preferably 50 parts by weight or less, and particularly preferably 30 parts by weight or less, relative to 100 parts by weight of component A.

[0211] (xiii) Other resins and elastomers In the polycarbonate resin composition of the present invention, other resins or elastomers may be used in small proportions in place of a part of the resin component of component A, as long as the effects of the present invention are exhibited. The amount of the other resins or elastomers is preferably 20% by weight or less, more preferably 10% by weight or less, and even more preferably 5% by weight or less, based on 100% by weight of the total with component A. Examples of such other resins include polyester resins such as polyethylene terephthalate and polybutylene terephthalate, polyamide resins, polyimide resins, polyetherimide resins, polyurethane resins, silicone resins, polyphenylene ether resins, polyphenylene sulfide resins, polysulfone resins, polymethacrylate resins, phenolic resins, and epoxy resins. Examples of elastomers include isobutylene / isoprene rubber, styrene / butadiene rubber, ethylene / propylene rubber, acrylic elastomers, polyester elastomers, polyamide elastomers, and core-shell elastomers such as MBS (methyl methacrylate / styrene / butadiene) rubber, MB (methyl methacrylate / butadiene) rubber, and MAS (methyl methacrylate / acrylonitrile / styrene) rubber.

[0212] (xiv) Other additives The polycarbonate resin composition of the present invention may contain other flow modifiers, antibacterial agents, dispersants such as liquid paraffin, photocatalytic antifouling agents, photochromic agents, and the like.

[0213] <Production of Resin Composition> Any method may be used to produce the resin composition of the present invention. For example, the A component, the B component, and any other components may be thoroughly mixed using a premixing means such as a V-type blender, a Henschel mixer, a mechanochemical device, or an extrusion mixer, and then granulated as necessary using an extrusion granulator or a briquetting machine, followed by melt kneading using a melt kneader such as a vented twin-screw extruder, and pelletizing using a device such as a pelletizer.

[0214] <Production of molded products> The resin composition of the present invention can be obtained by injection molding such pellets. In such injection molding, not only the usual cold runner type molding method but also hot runners that enable runnerless production can be used. In addition to the usual molding method, gas-assisted injection molding, injection compression molding, ultra-high speed injection molding, injection press molding, two-color molding, sandwich molding, in-mold coating molding, insert molding, foam molding (including those using supercritical fluids), rapid heating and cooling mold molding, heat insulating mold molding, and in-mold remelting molding, as well as molding methods consisting of combinations thereof, can be used for injection molding. Furthermore, various surface treatments can be performed on molded articles formed from the resin composition. Examples of surface treatments include decorative painting, hard coating, water-repellent and oil-repellent coating, hydrophilic coating, ultraviolet absorbing coating, infrared absorbing coating, electromagnetic wave absorbing coating, heat generating coating, antistatic coating, antistatic coating, conductive coating, and metallizing (plating, chemical vapor deposition (CVD), physical vapor deposition (PVD), thermal spraying, etc.).

[0215] (Low temperature impact strength) The polycarbonate resin composition of the present invention preferably has a notched Charpy impact strength of 30 kJ / m or less when a test piece cooled to -30°C is measured in accordance with ISO 179. 2 More preferably, it is 40 kJ / m or more. 2 More preferably, it is 50 kJ / m 2 The notched Charpy impact strength is 30 kJ / m or more. 2If it is less than this, it is difficult to apply it to outdoor structural members for cold regions, various housing members, and automobile-related parts.

[0216] (Appearance and color stability) The appearance of a three-tiered plate made using the polycarbonate resin composition of the present invention is characterized by only minor defects such as black discoloration due to black bumps, marbled appearance, surface peeling, color unevenness, and transmission unevenness, and it is more preferable that the above-mentioned appearance defects are not observed. If the above is not satisfied, it will lead to increased costs due to the occurrence of products with defective appearances, and a significant decrease in productivity due to the need to disassemble and clean the molding machine as a countermeasure, making it unsuitable for use as an exterior material. In addition, black discoloration due to black bumps is a problem that occurs when the color L during continuous molding is increased. * Fluctuation of ΔL * It can also be evaluated by the value, where L * is the CIE 1976 L standardized in JIS Z 8781-4. * a * b * It is a value that represents the lightness in a color space, and it reflects the effect of blackening caused by black spots with good sensitivity. The polycarbonate resin composition of the present invention has a L value measured in accordance with JIS Z 8781-4 for a molded product obtained by continuous molding at a molding temperature of 280°C for 25 shots. * Maximum color difference ΔL of the value * The value is preferably 3 or less, more preferably 2 or less, more preferably 1 or less, and even more preferably 0.5 or less. * If the value exceeds the above range, it may result in increased costs due to the occurrence of products with defective appearances, and a significant decrease in productivity due to the need to disassemble and clean the molding machine as a countermeasure, making the material unsuitable for use as an exterior material. EXAMPLES

[0217] The present invention will be described in more detail below with reference to examples, but these are not intended to limit the scope of the present invention. Unless otherwise specified, parts in the examples are parts by weight and % is % by weight. The evaluation was performed according to the following method.

[0218] (1) Viscosity average molecular weight (Mv) The specific viscosity (η SP ) was measured at 20°C using an Ostwald viscometer from a solution prepared by dissolving 0.7 g of polycarbonate resin pellets or polycarbonate-polydiorganosiloxane copolymer in 100 ml of methylene chloride. Specific viscosity (η SP )=(t-t0) / t0 [t0 is the number of seconds that methylene chloride falls, and t is the number of seconds that the sample solution falls] The specific viscosity (η SP ) and the viscosity average molecular weight Mv was calculated using the following formula: η SP / c=[η]+0.45×[η] 2 c (where [η] is the intrinsic viscosity) [η]=1.23×10 -4 Mv 0.83 c=0.7

[0219] (2) Polydiorganosiloxane component content and average polydiorganosiloxane repeat number (p+q) Using NMR JNM-AL400 manufactured by JEOL Ltd., polycarbonate-polydiorganosiloxane copolymer was measured. 1 The average chain length p+q was calculated by measuring the H-NMR spectrum and comparing the integral ratio of the peak derived from the dihydric phenol (I) with the integral ratio of the peak derived from the hydroxyaryl-terminated polydiorganosiloxane (II). Similarly, the average chain length p+q was calculated by comparing the integral ratio of the peak derived from the hydroxyaryl-terminated polydiorganosiloxane with the integral ratio of the peak derived from the polydiorganosiloxane.

[0220] (3) Average size of polydiorganosiloxane domains After drying component A with hot air at 120°C for 5 hours, it was molded in an injection molding machine (Japan Steel Works, Ltd., JSW Using a microtome (EM UC6 manufactured by Leica Microsystems), a molded piece measuring 10 mm in width, 80 mm in length, and 4.0 mm in thickness was molded at a molding temperature of 290°C, a mold temperature of 80°C, and a molding cycle of 50 seconds. A section of the intersection 15 mm from the gate and 5 mm from the side end of the obtained molded piece, 2 mm deep, was cut perpendicular to the direction of resin flow using a microtome (EM UC6 manufactured by JEOL Ltd.). Ultrathin sections were then prepared by cutting the area perpendicular to the direction of resin flow using a grid (EM The particles were attached to a FINE GRID No. 2632 F-200-CU 100PC / CA and observed at an accelerating voltage of 200 kV using a TEM JEM-2100 manufactured by JEOL Ltd. The observation magnification was 20,000 times. The obtained micrographs were subjected to particle analysis using image analysis software Win ROOF Ver. 6.6 (Mitani Shoji Co., Ltd.) to obtain the average size of the polydiorganosiloxane domains in the sample slices. Here, the maximum major axis (the length when any two points on the outer contour of the particle are selected so that the length between them is the maximum) was used as the size of each domain. The same analysis was performed on five sample slices, and the average value was used as the value for each sample.

[0221] (4) Visual appearance of molded specimen and ΔL * The resin composition pellets were dried with hot air at 120°C for 5 hours, and then 25 square plates with a width of 50 mm, length of 100 mm, and thickness of 2 mm were continuously molded using an injection molding machine (NEX50-5E, manufactured by Nissei Plastic Industrial Co., Ltd.) at a molding temperature of 280°C, a mold temperature of 70°C, and a molding cycle of 40 seconds, and the appearance was evaluated visually. Appearance defects included blackening due to black spots, marbled appearance, and surface peeling on the bent surface when the square plate was bent by 90°, and the evaluation was based on the presence and degree of each.

[0222] [Black stuff] ⊚: No blackening due to black spots is observed. ○: Blackening due to black spots is slight, gradually subsiding, or the occurrence frequency is 20% or less. ×: There is noticeable blackening due to black spots. [Marble look] ⊚: No defects in marble-like appearance. ◯: There is some defect in the marbled appearance, but it is minor. ×: There is noticeable glare and poor marbled appearance. [Surface peeling] ⊚: No surface peeling is observed. ○: Surface peeling is observed, but it is minor. ×: Significant surface peeling is observed.

[0223] The obtained molded pieces were measured in accordance with JIS Z 8781-4 using a spectrophotometer CE-7000A (Greta Macbeth) with a D65 light source, a 10-degree visual field, and a reflection method according to CIE 1976 L * a * b * Lightness L * The L value of the 25 pieces obtained was measured. * The highest value of L * Value and lowest L * The difference in values ​​is the maximum color difference ΔL * The value was set as

[0224] (5) Low-temperature impact strength evaluation (notched Charpy impact strength) The pellets of the resin composition were dried with hot air at 120°C for 5 hours, and then injection molded (FANUC, ROBOSHOT α-S100iA) to produce molded pieces with a width of 10 mm, length of 80 mm, and thickness of 4.0 mm at a molding temperature of 290°C, a mold temperature of 80°C, and a molding cycle of 40 seconds. The notched Charpy impact strength of the test pieces cooled to -30°C was measured in accordance with ISO179.

[0225] [Both ends of phenol-modified polydiorganosiloxane] In the examples and comparative examples, a polydiorganosiloxane compound having the following structure was used as the dihydric phenol (II) having a polydiorganosiloxane structure. (II)-1: p+q=40 (KF-2201, manufactured by Shin-Etsu Chemical Co., Ltd.) (II)-2: p+q=90 (KF-2102 manufactured by Shin-Etsu Chemical Co., Ltd.) (II)-3: 2-allylphenol-terminated polydimethylsiloxane with p+q=130, synthesized according to the method for producing 2-allylphenol-terminated polydiorganosiloxane described in Japanese Patent Publication No. 2662310.

[0226] [Production of polycarbonate-polydiorganosiloxane copolymer] PC-POS-1 to PC-POS-6 were produced by the following method. The properties of each copolymer are shown in Table 1. (PC-POS-1 manufacturing method) A reactor equipped with a thermometer, stirrer, and reflux condenser was charged with 17,590 parts of ion-exchanged water and 6,883 parts of 25% aqueous sodium hydroxide solution, and 3,748 parts (16.41 moles) of 2,2-bis(4-hydroxyphenyl)propane (bisphenol A) as the dihydric phenol (I) represented by the general formula [5] and 7.5 parts of hydrosulfite were dissolved therein. Then, 11,246 parts of methylene chloride (8 molar equivalents relative to the total amount of dihydric phenols) was added, and 1,900 parts of phosgene was blown in over a period of 70 minutes at 16 to 24°C with stirring. A solution of 1324 parts of 25% sodium hydroxide aqueous solution and 149 parts of p-tert-butylphenol dissolved in 1342 parts of methylene chloride (0.96 molar equivalents based on the total amount of dihydric phenols) was added, and while stirring, a solution of 397 parts (0.128 moles) of the above KF-2201 as dihydric phenol (II) represented by the general formula [6] dissolved in 214 parts of methylene chloride (0.15 molar equivalents based on the total amount of dihydric phenols) was added, and then a solution of 264 parts (0.037 moles) of KF-2102 dissolved in 142 parts of methylene chloride (0.10 molar equivalents based on the total amount of dihydric phenols) was added to emulsify the mixture, and the mixture was stirred vigorously again. Under such stirring, 4.2 parts of triethylamine was added when the reaction solution was at 26°C, and 15 minutes later, 2795 parts of methylene chloride (2 molar equivalents relative to the total amount of dihydric phenols) was added. After adding triethylamine, the reaction was terminated by continuing stirring for 1 hour at a temperature of 26-31°C. After the reaction was terminated, the organic phase was separated, diluted with methylene chloride and washed with water, then acidified with hydrochloric acid and washed with water. When the conductivity of the aqueous phase became almost the same as that of ion-exchanged water, the mixture was put into a kneader filled with warm water, and the methylene chloride was evaporated while stirring to obtain a powder of polycarbonate-polydiorganosiloxane copolymer. After dehydration, the mixture was dried for 12 hours at 120°C using a hot air circulation dryer. The resulting polycarbonate-polydiorganosiloxane copolymer had an average polydiorganosiloxane repeat number (p+q) of 52, a viscosity average molecular weight of 16,000, a polydiorganosiloxane component content of 12.5 weight %, an average polydiorganosiloxane domain size of 42 nm, 13 polydiorganosiloxane domains with a maximum length of 80 nm or more, and 0 polydiorganosiloxane domains with a maximum length of 400 nm or more.

[0227] (PC-POS-2 manufacturing method) The same production method as in PC-POS-1 was used, except that a solution of 198 parts (0.064 moles) of the above KF-2201 as the dihydric phenol (II) represented by the general formula [6] dissolved in 100 parts of methylene chloride (0.07 molar equivalents relative to the total amount of dihydric phenols) was added, and then a solution of 463 parts (0.064 moles) of KF-2102 dissolved in 230 parts of methylene chloride (0.16 molar equivalents relative to the total amount of dihydric phenols) was added. The resulting polycarbonate-polydiorganosiloxane copolymer had an average polydiorganosiloxane repeat number (p+q) of 67, a viscosity average molecular weight of 16,100, a polydiorganosiloxane component content of 12.5 weight %, an average polydiorganosiloxane domain size of 59 nm, 17 polydiorganosiloxane domains with a maximum length of 80 nm or more, and 0 polydiorganosiloxane domains with a maximum length of 400 nm or more.

[0228] (PC-POS-3 manufacturing method) The same manufacturing method as PC-POS-1 was used, except that a solution of 661 parts (0.091 moles) of the above KF-2102 dissolved in 356 parts of methylene chloride (0.25 molar equivalents relative to the total amount of dihydric phenol) was added as the dihydric phenol (II) represented by the general formula [6]. The polycarbonate-polydiorganosiloxane copolymer obtained had an average polydiorganosiloxane repeat number (p+q) of 90, a viscosity average molecular weight of 16,000, a polydiorganosiloxane content of 12.6% by weight, an average size of the polydiorganosiloxane domains of 69 nm, 32 polydiorganosiloxane domains with a maximum length of 80 nm or more, and 0 polydiorganosiloxane domains with a maximum length of 400 nm or more.

[0229] (PC-POS-4 manufacturing method) The same manufacturing method as PC-POS-1 was used, except that 661 parts (0.066 moles) of the above (II)-3 (repeating number p+q=130) was dissolved in 356 parts of methylene chloride (0.25 molar equivalents relative to the total amount of dihydric phenol) as the dihydric phenol (II) represented by the general formula [6] was added. The polycarbonate-polydiorganosiloxane copolymer obtained had an average polydiorganosiloxane repeating number (p+q) of 130, a viscosity average molecular weight of 16,100, a polydiorganosiloxane content of 12.7% by weight, an average size of the polydiorganosiloxane domains of 92 nm, 43 polydiorganosiloxane domains with a maximum length of 80 nm or more, and 0 polydiorganosiloxane domains with a maximum length of 400 nm or more.

[0230] (PC-POS-5 manufacturing method) The same production method as in PC-POS-1 was used, except that a solution of 66 parts (0.021 mole) of the above KF-2201 as the dihydric phenol (II) represented by the general formula [6] dissolved in 33 parts of methylene chloride (0.021 molar equivalent relative to the total amount of dihydric phenols) was added, followed by the addition of a solution of 154 parts (0.021 mole) of KF-2102 dissolved in 77 parts of methylene chloride (0.06 molar equivalent relative to the total amount of dihydric phenols), and a solution of 99 parts of p-tert-butylphenol dissolved in 891 parts of methylene chloride (0.64 molar equivalent relative to the total amount of dihydric phenols). The resulting polycarbonate-polydiorganosiloxane copolymer had an average polydiorganosiloxane repeat number (p+q) of 67, a viscosity average molecular weight of 20,000, a polydiorganosiloxane component content of 4.4 weight %, an average polydiorganosiloxane domain size of 31 nm, the number of polydiorganosiloxane domains having a maximum length of 80 nm or more was 4, and the number of polydiorganosiloxane domains having a maximum length of 400 nm or more was 0.

[0231] (PC-POS-6 manufacturing method) A polycarbonate-polydiorganosiloxane copolymer produced under the production conditions of Example 8 described in WO2011 / 013846. 21592 parts of ion-exchanged water and 3675 parts of 48.5% aqueous sodium hydroxide solution were placed in a reactor equipped with a thermometer, a stirrer, and a reflux condenser, and 3880 parts (17.00 moles) of 2,2-bis(4-hydroxyphenyl)propane (bisphenol A) as the dihydric phenol (I) represented by the general formula [5] and 7.6 parts of hydrosulfite were dissolved therein. Then, 14565 parts of methylene chloride (10 molar equivalents relative to the total amount of dihydric phenols) was added, and 1900 parts of phosgene was blown in over 60 minutes at 22 to 30°C while stirring. Add 7283 parts of methylene chloride (5 molar equivalents relative to the total amount of dihydric phenols), add 1131 parts of 48.5% aqueous sodium hydroxide solution, and add a solution of 108 parts of p-tert-butylphenol dissolved in 800 parts of methylene chloride (0.55 molar equivalents relative to the total amount of dihydric phenols), and add 430 parts (0.139 moles) of the above KF-2201 as dihydric phenol (II) represented by the general formula [6] dissolved in 800 parts of methylene chloride (0.55 molar equivalents relative to the total amount of dihydric phenols) at a rate of 0.0004 molar equivalents / min relative to dihydric phenol (I) to emulsify, then stir vigorously again. Under such stirring, add 4.3 parts of triethylamine when the reaction liquid is at 26°C, and continue stirring at a temperature of 26-31°C for 1 hour to complete the reaction. After the reaction was completed, the organic phase was separated, diluted with methylene chloride, washed with water, and then acidified with hydrochloric acid and washed with water. When the conductivity of the aqueous phase was almost the same as that of ion-exchanged water, it was put into a kneader filled with warm water and the methylene chloride was evaporated while stirring to obtain a polycarbonate-polydiorganosiloxane copolymer powder. After dehydration, it was dried at 120°C for 12 hours in a hot air circulation dryer. The polycarbonate-polydiorganosiloxane copolymer obtained had an average polydiorganosiloxane repeat number (p+q) of 40, a viscosity average molecular weight of 19,400, a polydiorganosiloxane component content of 8.4% by weight, an average size of polydiorganosiloxane domains of 10 nm, the number of polydiorganosiloxane domains with a maximum length of 80 nm or more was 0, and the number of polydiorganosiloxane domains with a maximum length of 400 nm or more was 0.

[0232] [Table 1]

[0233] (PC-1) Linear aromatic polycarbonate resin powder with a solution viscosity of 23,900 molecular weight and a repeating skeleton of 2,2-bis(4-hydroxyphenyl)propane (Teijin Ltd. Panlite L-1250WP)

[0234] (B component) B-1: (Meth)acrylic modified polyorganosiloxane (Chaline, manufactured by Nissin Chemical Co., Ltd.) R170 (trade name), a graft copolymer using polydimethylsiloxane as component B1 and methyl methacrylate as component B2, polydimethylsiloxane content 70% by weight B-2 (Comparative Example): Polydimethyl silicone (KF96-1000cs (product name) manufactured by Shin-Etsu Chemical Co., Ltd.) B-3 (Comparative Example): Polymethyl methacrylate resin (Acrypet VH001 (product name) manufactured by Mitsubishi Chemical Corporation)

[0235] (C component) C-1: Cyclic phenoxyphosphazene (Fushimi Pharmaceutical Co., Ltd., Rabitol FP-110T (product name))

[0236] (D component) D-1: A polytetrafluoroethylene-based mixture, a mixture of polytetrafluoroethylene acrylic copolymers produced by emulsion polymerization (polytetrafluoroethylene content: 50% by weight) (Mitsubishi Rayon Co., Ltd., Metablen A3750 (product name))

[0237] (Other Ingredients) E-1: 3-(3,5-di-tert-butyl-4-hydroxyphenyl) stearyl propionate (manufactured by BASF Japan Ltd.: Irganox 1076 (trade name)) E-2: Tris(2,4-di-tert-butylphenyl) phosphite (Irgafos168 (trade name) manufactured by BASF Japan Ltd.) F-1: UV absorber (ADEKA STAB LA-31 (product name) manufactured by ADEKA CORPORATION) TiO2: Titanium dioxide (Ishihara Sangyo Kaisha, Ltd., TYPAQUE PC-3 (product name))

[0238] [Production of polycarbonate resin composition] Components A to D and various additives were weighed according to the compositions shown in Tables 2 and 3, mixed uniformly using a blender, and melt-kneaded using a vented twin-screw extruder to obtain pellets. The various additives used were premixed with polycarbonate resin in advance at a concentration of 10 to 100 times the amount of each additive, and then the entire mixture was mixed using a blender. The vented twin-screw extruder used was a KTX-30 (diameter 30 mmφ) made by Kobe Steel, Ltd. Strands were extruded under the conditions of cylinder temperature and die temperature of 280°C, screw rotation speed of 150 rpm, discharge rate of 20 kg / h, and vent suction degree of 3 kPa, and after cooling in a water bath, the strands were cut using a pelletizer and pelletized. The results of various evaluations are shown in Tables 2 and 3.

[0239] [Table 2]

[0240] [Table 3]

[0241] [Examples 1 to 10, Comparative Examples 1 to 8] As is clear from the above table, the compositions of Examples 1 to 10 have a melting point of 40 kJ / m 2It can be seen that the poor black appearance due to black spots, the marbled appearance, and the surface peeling are suppressed while showing good low-temperature impact resistance exceeding 1000 MPa. In contrast, Comparative Examples 1 and 2, which do not contain the B component or have a small amount of the B component, cause poor black appearance due to black spots. On the other hand, Comparative Example 3, which has a large amount of the B component, and Comparative Example 7, which uses a PC-POS copolymer with a large POS repeat number, cause strong marbled appearance defects and also cause surface peeling. On the other hand, Comparative Example 6, which uses a PC-POS copolymer with a small POS repeat number, and Comparative Example 8, which does not use a PC-POS copolymer, cause poor low-temperature impact resistance. In addition, Comparative Examples 4 and 5, which use a polyorganosiloxane or (meth)acrylic resin that is not (meth)acrylic-modified as the B component, cause poor black appearance due to black spots.

Claims

1. (A) A polycarbonate resin composition comprising (A-1) 1 to 100 parts by weight of a polycarbonate-polydiorganosiloxane copolymer consisting of a polycarbonate block represented by the following general formula [1] and a polydiorganosiloxane block represented by the following general formula [3], and (A-2) 100 parts by weight of a resin component (A component) consisting of 0 to 99 parts by weight of an aromatic polycarbonate resin consisting of a polycarbonate block represented by the following general formula [1], and (B) 0.3 to 2.5 parts by weight of a (meth)acrylic-modified polyorganosiloxane (B component). 【Chemistry 1】 [(In the above general formula [1], R 1 and R 2 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of each of these groups, they may be the same or different, e and f each represent an integer of 1 to 4, and W represents a single bond or at least one group selected from the group consisting of groups represented by the following general formula [2]: 【Chemistry 2】 (In the above general formula [2], R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 and R 18 each independently represents a group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms; R 19 and R 20 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of groups, they may be the same or different, g is an integer from 1 to 10, and h is an integer from 4 to 7. 【Chemistry 3】 (In the above general formula [3], R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; R 9 and R 10 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and the average chain length p+q is a natural number from 50 to 120. X is a divalent aliphatic group having 2 to 8 carbon atoms.

2. 2. The polycarbonate resin composition according to claim 1, wherein p+q in the above formula [3] is 50 to 70.

3. 3. The polycarbonate resin composition according to claim 1, wherein the content of the polydiorganosiloxane block represented by the formula [3] in the component A-1 is 4 to 20% by weight.

4. 4. The polycarbonate resin composition according to claim 1, wherein the content of the polydiorganosiloxane block represented by the formula [3] in Component A is 2.5 to 6.5% by weight.

5. 5. The polycarbonate resin composition according to claim 1, wherein the viscosity average molecular weight of component A-1 is 11,000 to 30,000.

6. 6. The polycarbonate resin composition according to any one of claims 1 to 5, wherein the polydiorganosiloxane block represented by the formula [3] is a polydiorganosiloxane block derived from a (2-allylphenol)-terminated polydiorganosiloxane or a (2-methoxy-4-allylphenol)-terminated polydiorganosiloxane.

7. R in the above formula [3] 3 , R 4 , R 5 , R 6 , R 7 and R 8 The polycarbonate resin composition according to any one of claims 1 to 6, wherein is a methyl group.

8. 8. The polycarbonate resin composition according to any one of claims 1 to 7, wherein the polycarbonate block represented by the formula [1] is a polycarbonate block derived from 2,2-bis(4-hydroxyphenyl)propane.

9. The polycarbonate resin composition according to any one of claims 1 to 8, characterized in that the B component is a (meth)acrylic-modified polyorganosiloxane obtained by graft copolymerizing a (meth)acrylic acid ester (B2 component) with a polyorganosiloxane (B1 component) represented by the following general formula [4]. 【Chemistry 4】 [In the above general formula [4], R 1 , R 2 and R 3 each independently represents a hydrocarbon group having 1 to 20 carbon atoms or a halogenated hydrocarbon group having 1 to 20 carbon atoms, and Y represents an organic group having at least one group selected from the group consisting of a vinyl group, an allyl group, and a γ-(meth)acryloxypropyl group, and an SH group. 1 and X 2 each independently represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or SiR 4 R 5 R 6 (R 4 , R 5 each independently represents a hydrocarbon group having 1 to 20 carbon atoms or a halogenated hydrocarbon group having 1 to 20 carbon atoms; R 6 represents an organic group having at least one group selected from the group consisting of a hydrocarbon group having 1 to 20 carbon atoms, a halogenated hydrocarbon group having 1 to 20 carbon atoms, or a radical reactive group selected from the group consisting of a vinyl group, an allyl group, and a γ-(meth)acryloxypropyl group, and an SH group), m is an integer of 1 to 10,000, n is an integer of 1 or more, and the siloxane chain may be branched.]

10. In the above formula [4], R 1 , R 2 , R 3 The polycarbonate resin composition according to claim 9, wherein is a methyl group.

11. 11. The polycarbonate resin composition according to claim 9, wherein component B2 is methyl methacrylate and / or 2-hydroxyethyl methacrylate.

12. The L measured in accordance with JIS Z 8781-4 for the molded product obtained by continuous molding for 25 shots at a molding temperature of 280°C. * Maximum color difference ΔL * 12. The polycarbonate resin composition according to claim 1, wherein the value is 3 or less.

13. 13. The polycarbonate resin composition according to claim 1, further comprising 0.001 to 20 parts by weight of a flame retardant (C) (Component C) per 100 parts by weight of Component A.

14. The polycarbonate resin composition according to any one of claims 1 to 13, further comprising 0.01 to 5 parts by weight of a fluorinated anti-dripping agent (D) per 100 parts by weight of the A component.

15. A molded article formed from the polycarbonate resin composition according to any one of claims 1 to 14.

Citation Information

Patent Citations

  • Polycarbonate resin composition

    JP1992225060A

  • Polycarbonate-polysiloxane block copolymer

    JP1993247195A

  • Polycarbonate resin composition

    JP2000302958A

  • Translucent thermoplastic resin composition, method for producing the same, and molded product

    JP2006523243A

  • Slidable resin composition and molded article formed therefrom

    JP2009035625A